Tinted glass article with improved mechanical durability
By adjusting the composition and heat treatment process of the glass composition, a colored glass product with excellent mechanical properties and color is prepared, which solves the problems of poor color and insufficient strength in the prior art.
Patent Information
- Application Number
- CN202311023161.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-02-22
- Filing Date
- 2022-06-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-06-17
AI Technical Summary
The existing aluminosilicate glass compositions are difficult to produce the desired color after simply including the colorant, while lacking colored glass products of high strength and fracture toughness.
By adjusting the chemical composition of the glass composition, the colored glass products with excellent ion exchangeability and drop properties were prepared by heat treatment under F2 illumination, and heat treatment under F2 illumination, the colored glass products with excellent ion exchangeability and drop properties were prepared.
It is achieved to produce the desired colored glass products while maintaining excellent mechanical properties and ion exchange properties, meeting the needs of high strength and fracture toughness.
Smart Images

Figure CN116854368B_ABST
Abstract
Description
[0001] This application is a divisional application of a patent application with application number 202280008622.1, application date June 17, 2022, and name “Colored glass product with improved mechanical durability”.
[0002] This application claims the benefit of priority to U.S. application serial number 17 / 677,345 filed on February 22, 2022, U.S. application serial number 17 / 677,375 filed on February 22, 2022, U.S. provisional application serial number 63 / 304,807 filed on January 31, 2022, U.S. provisional application serial number 63 / 251,785 filed on October 4, 2021, and U.S. provisional application serial number 63 / 212,191 filed on June 18, 2021, the contents of each of which are relied upon and incorporated herein by reference in their entirety. Technical Field
[0003] The present description relates generally to glass compositions and glass articles, and more particularly to glass compositions and ion-exchangeable tinted glass articles formed therefrom. Background Art
[0004] Aluminosilicate glass articles may exhibit excellent ion exchange and drop performance. Various industries, including the consumer electronics industry, desire colored materials with the same or similar strength and fracture toughness properties. However, simply including a colorant in a conventional aluminosilicate glass composition may not produce the desired color.
[0005] Therefore, there is a need for alternative tinted glass articles having high strength and fracture toughness. Summary of the invention
[0006] According to the first aspect A1, the colored glass article may include: greater than or equal to 50 mol % and less than or equal to 80 mol % of SiO 2 ; greater than or equal to 7 mol% and less than or equal to 25 mol% Al 2 O 3 ; greater than or equal to 1 mol% and less than or equal to 15 mol% B 2 O 3 ; greater than or equal to 5 mol% and less than or equal to 20 mol% Li 2 O; 0.5 mol% or more and 15 mol% or less of Na 2 O; K greater than 0 mol% and less than or equal to 1 mol% 2 O; and greater than or equal to 1×10 -6 mol% and less than or equal to 1 mol% Au, where: R 2 O-Al2 O 3 Greater than or equal to -5 mol% and less than or equal to 7 mol%, R 2 O is Li 2 O、Na 2 O and K 2 The sum of O.
[0007] According to the second first aspect A1.1, the colored glass article may comprise: greater than or equal to 50 mol % and less than or equal to 80 mol % of SiO 2 ; greater than or equal to 7 mol% and less than or equal to 25 mol% Al 2 O 3 ; greater than or equal to 1 mol% and less than or equal to 15 mol% B 2 O 3 ; greater than or equal to 7 mol% and less than or equal to 20 mol% Li 2 O; 0.5 mol% or more and 12 mol% or less of Na 2 O; K greater than 0 mol% and less than or equal to 1 mol% 2 O; and greater than or equal to 1×10 -6 mol% and less than or equal to 1 mol% Au, where: R 2 O-Al 2 O 3 Greater than or equal to -5 mol% and less than or equal to 5 mol%, R 2 O is Li 2 O、Na 2 O and K 2 The sum of O.
[0008] The second aspect A2 includes the tinted glass article according to the first aspect A1 or the second aspect A1.1, wherein the transmittance color coordinates of the tinted glass article in the CIELAB color space measured under F2 illumination with an article thickness of 1.33 mm and a standard observation angle of 10° are: L* greater than or equal to 50 and less than or equal to 100; a* greater than or equal to -15 and less than or equal to 25; and b* greater than or equal to -25 and less than or equal to 25.
[0009] A third aspect A3 includes the tinted glass article according to the second aspect A2, wherein R 2 O-Al 2 O 3 Greater than or equal to −5 mol % and less than or equal to 1.5 mol %; and wherein b* is greater than or equal to −25 and less than or equal to 10.
[0010] A fourth aspect A4 includes the tinted glass article according to the third aspect A3, wherein R2 O-Al 2 O 3 Greater than or equal to -3 mol % and less than or equal to 1.5 mol %; and wherein b* is greater than or equal to -15 and less than or equal to 7.
[0011] A fifth aspect A5 includes the tinted glass article according to the second aspect A2, wherein R 2 O-Al 2 O 3 greater than 1.5 mol % and less than or equal to 7 mol %; and wherein b* is greater than or equal to 0 and less than or equal to 25.
[0012] A sixth aspect A6 includes the tinted glass article according to the fifth aspect A5, wherein R 2 O-Al 2 O 3 greater than 1.5 mol % and less than or equal to 5 mol %; and wherein b* is greater than or equal to 0 and less than or equal to 15.
[0013] A seventh aspect A7 includes the colored article according to any one of the first to sixth aspects A1 to A6, wherein R 2 O-Al 2 O 3 Greater than or equal to -3 mol% and less than or equal to 5 mol%.
[0014] The eighth aspect A8 includes the tinted glass article according to the seventh aspect A7, wherein R 2 O-Al 2 O 3 Greater than or equal to -1 mol% and less than or equal to 3 mol%.
[0015] A ninth aspect A9 includes the colored article according to any one of the first to eighth aspects A1 to A8, wherein the colored glass article includes greater than or equal to 0.0001 mol % and less than or equal to 0.1 mol % Au.
[0016] The tenth aspect A10 includes the colored article according to any one of the first to ninth aspects A1 to A9, wherein R 2 O is greater than or equal to 6 mol % and less than or equal to 25 mol %.
[0017] The eleventh aspect A11 includes the tinted glass article according to the tenth aspect A10, wherein R 2 O is greater than or equal to 8 mol % and less than or equal to 23 mol %.
[0018] The twelfth aspect A12 includes the colored article according to any one of the first to eleventh aspects A1 to A11, wherein the colored glass article comprises greater than or equal to 0.01 mol % and less than or equal to 2 mol % of ZrO. 2 .
[0019] The thirteenth aspect A13 includes the colored glass article according to the twelfth aspect A12, wherein the colored glass article comprises greater than or equal to 0.1 mol % and less than or equal to 1.5 mol % of ZrO 2 .
[0020] A fourteenth aspect A14 includes the colored article according to any one of the first to thirteenth aspects A1 to A13, wherein the colored glass article comprises greater than or equal to 0.01 mol % and less than or equal to 1 mol % of Fe 2 O 3 .
[0021] The fifteenth aspect A15 includes the colored article according to the fourteenth aspect A14, wherein the colored glass article comprises greater than or equal to 0.05 mol % and less than or equal to 0.5 mol % of Fe 2 O 3 .
[0022] The sixteenth aspect A16 comprises the colored article of any one of the first to fifteenth aspects A1 to A15, wherein 5.72*Al 2 O 3 (mol%)-21.4*ZnO(mol%)-2.5*P 2 O 5 (mol%)-35*Li 2 O(mol%)-16.6*B 2 O 3 (mol%)-20.5*MgO (mol%)-23.3*Na 2 O(mol%)-27.9*SrO(mol%)-18.5*K 2 O (mol%) -26.3*CaO (mol%) is greater than -609 mol%.
[0023] A seventeenth aspect A17 includes the colored glass article according to any one of the first to sixteenth aspects A1 to A16, wherein the colored glass article comprises greater than or equal to 0.01 mol % and less than or equal to 1 mol % SnO 2 .
[0024] The eighteenth aspect A18 includes the colored glass article according to the seventeenth aspect A17, wherein the colored glass article comprises greater than or equal to 0.05 mol % and less than or equal to 0.75 mol % SnO 2 .
[0025] The nineteenth aspect A19 includes the tinted glass article of any of the first to eighteenth aspects A1 to A18, wherein the tinted glass article is substantially free of MgO, CaO, ZnO, Cl, or combinations thereof.
[0026] A twentieth aspect A20 includes the tinted glass article of any one of the first to nineteenth aspects A1 to A19, wherein the tinted glass article comprises greater than or equal to 7 mol % and less than or equal to 18 mol % of Li 2 O.
[0027] The twenty-first aspect A21 includes the tinted glass article of the twentieth aspect A20, wherein the tinted glass article comprises greater than or equal to 9 mol % and less than or equal to 16 mol % of Li 2 O.
[0028] The twenty-second aspect A22 includes the tinted glass article of any one of the first to twenty-first aspects A1 to A21, wherein the tinted glass article comprises greater than or equal to 1 mol % and less than or equal to 12 mol % of Na 2 O.
[0029] The twenty-third aspect A23 includes the tinted glass article of the twenty-second aspect A22, wherein the tinted glass article comprises greater than or equal to 2 mol % and less than or equal to 10 mol % of Na 2 O.
[0030] The twenty-second aspect A24 includes the tinted glass article of any one of the first to twenty-third aspects A1 to A23, wherein the tinted glass article comprises greater than or equal to 0.1 mol % and less than or equal to 0.5 mol % of K 2 O.
[0031] The twenty-fifth aspect A25 includes the tinted glass article of any one of the first to twenty-fourth aspects A1 to A24, wherein the tinted glass article comprises greater than or equal to 9 mol % and less than or equal to 23 mol % of Al 2 O 3 .
[0032] The twenty-sixth aspect A26 includes the tinted glass article of the twenty-fifth aspect A25, wherein the tinted glass article comprises greater than or equal to 11 mol % and less than or equal to 20 mol % of Al2 O 3 .
[0033] The twenty-seventh aspect A27 includes the tinted glass article of any one of the first to twenty-sixth aspects A1-A26, wherein the tinted glass article comprises greater than or equal to 2 mol % and less than or equal to 12 mol % of B 2 O 3 .
[0034] The twenty-eighth aspect A28 includes the tinted glass article of the twenty-seventh aspect A27, wherein the tinted glass article comprises greater than or equal to 3 mol % and less than or equal to 10 mol % of B 2 O 3 .
[0035] The twenty-ninth aspect A29 includes the tinted glass article according to any one of the first to twenty-eighth aspects A1 to A28, wherein the tinted glass article comprises greater than or equal to 52 mol % and less than or equal to 75 mol % SiO 2 .
[0036] The 30th aspect A30 includes the tinted glass article according to any one of the first to twenty-ninth aspects A1 to A29, wherein the tinted glass article has a thickness greater than or equal to 250 μm and less than or equal to 6 mm.
[0037] The thirty-first aspect A31 includes the tinted glass article of any of the first to thirtieth aspects A1 to A30, wherein the tinted glass article is an ion-exchanged tinted glass article.
[0038] The thirty-second aspect A32 includes the tinted glass article of the thirty-first aspect A31, wherein the ion-exchanged tinted glass article has a compression depth of 10 μm or greater.
[0039] The thirty-third aspect A33 includes the tinted glass article of the thirty-first aspect A31 or the thirty-second aspect A32, wherein the ion-exchanged tinted glass article has a thickness "t" and a compression depth greater than or equal to 0.15 t.
[0040] Thirty-fourth aspect A34 includes the tinted glass article of any of thirty-first to thirty-third aspects A31 to A33, wherein the ion-exchanged tinted glass article has a surface compressive stress greater than or equal to 300 MPa.
[0041] Thirty-fifth aspect A35 includes the tinted glass article of any of thirty-first to thirty-fourth aspects A31 to A34, wherein the ion-exchanged tinted glass article has a maximum central tension greater than or equal to 40 MPa.
[0042] According to the thirty-sixth aspect A36, a consumer electronic device may include: a shell having a front surface, a rear surface and a side surface; and electronic components at least partially arranged in the shell, the electronic components including at least a controller, a memory and a display, and the display is arranged at the front surface of the shell or adjacent to the front surface of the shell; wherein the shell contains a colored glass product according to any one of the first to thirty-fifth aspects A1 to A35.
[0043] According to the thirty-seventh aspect A37, the glass composition may include: greater than or equal to 50 mol% and less than or equal to 80 mol% of SiO 2 ; greater than or equal to 7 mol% and less than or equal to 25 mol% Al 2 O 3 ; greater than or equal to 1 mol% and less than or equal to 15 mol% B 2 O 3 ; greater than or equal to 5 mol% and less than or equal to 20 mol% Li 2 O; 0.5 mol% or more and 15 mol% or less of Na 2 O; K greater than 0 mol% and less than or equal to 1 mol% 2 O; and greater than or equal to 1×10 -6 mol% and less than or equal to 1 mol% Au, where: R 2 O-Al 2 O 3 Greater than or equal to -5 mol% and less than or equal to 7 mol%, R 2 O is Li 2 O、Na 2 O and K 2 The sum of O.
[0044] According to the second thirty-seventh aspect A37.1, the glass composition may include: greater than or equal to 50 mol% and less than or equal to 80 mol% SiO 2 ; greater than or equal to 7 mol% and less than or equal to 25 mol% Al 2 O 3 ; greater than or equal to 1 mol% and less than or equal to 15 mol% B 2 O 3 ; greater than or equal to 7 mol% and less than or equal to 20 mol% Li 2 O; 0.5 mol% or more and 12 mol% or less of Na 2 O; K greater than 0 mol% and less than or equal to 1 mol% 2 O; and greater than or equal to 1×10-6 mol% and less than or equal to 1 mol% Au, where: R 2 O-Al 2 O 3 Greater than or equal to -5 mol% and less than or equal to 5 mol%, R 2 O is Li 2 O、Na 2 O and K 2 The sum of O.
[0045] Thirty-eighth aspect A38 includes the glass composition of aspect A37 or aspect A37.1, wherein R 2 O-Al 2 O 3 Greater than or equal to -3 mol% and less than or equal to 5 mol%.
[0046] Thirty-ninth aspect A39 includes the glass composition of thirty-eighth aspect A38, wherein R 2 O-Al 2 O 3 Greater than or equal to -1 mol% and less than or equal to 3 mol%.
[0047] The fortieth aspect A40 includes the glass composition according to the thirty-seventh to thirty-ninth aspects A37 to A39, wherein the glass composition comprises greater than or equal to 0.0001 mol % and less than or equal to 0.1 mol % Au.
[0048] The forty-first aspect A41 includes the glass composition of any one of the thirty-seventh to fortieth aspects A37 to A40, wherein R 2 O is greater than or equal to 6 mol % and less than or equal to 25 mol %.
[0049] The forty-second aspect A42 includes the glass composition according to the forty-first aspect A41, wherein R 2 O is greater than or equal to 8 mol % and less than or equal to 23 mol %.
[0050] A forty-third aspect A43 includes the glass composition according to any one of the thirty-seventh to forty-second aspects A37 to A42, wherein the glass composition comprises greater than or equal to 0.01 mol% and less than or equal to 2 mol% of ZrO 2 .
[0051] The forty-fourth aspect A44 includes the glass composition of the forty-third aspect A43, wherein the glass composition comprises greater than or equal to 0.1 mol% and less than or equal to 1.5 mol% of ZrO 2 .
[0052] Aspect A45 of the forty-fifth aspect includes the glass composition of any one of aspects A37 to A44 of the thirty-seventh to forty-fourth aspects, wherein the glass composition comprises greater than or equal to 0.01 mol % and less than or equal to 1 mol % of Fe. 2 O 3 .
[0053] The forty-sixth aspect A46 includes the glass composition according to the forty-fifth aspect A45, wherein the glass composition comprises greater than or equal to 0.05 mol% and less than or equal to 0.5 mol% of Fe. 2 O 3 .
[0054] A47 of the forty-seventh aspect includes the glass composition of any one of the thirty-seventh to forty-sixth aspects A37 to A46, wherein 5.72*Al 2 O 3 (mol%)-21.4*ZnO(mol%)-2.5*P 2 O 5 (mol%)-35*Li 2 O(mol%)-16.6*B 2 O 3 (mol%)-20.5*MgO (mol%)-23.3*Na 2 O(mol%)-27.9*SrO(mol%)-18.5*K 2 O (mol%) -26.3*CaO (mol%) is greater than -609 mol%.
[0055] A forty-eighth aspect A48 includes the glass composition according to any one of the thirty-seventh to forty-seventh aspects A37 to A47, wherein the glass composition comprises greater than or equal to 0.01 mol% and less than or equal to 1 mol% of SnO 2 .
[0056] The forty-ninth aspect A49 includes the glass composition according to the forty-eighth aspect A48, wherein the glass composition comprises greater than or equal to 0.05 mol% and less than or equal to 0.75 mol% of SnO 2 .
[0057] Fiftieth aspect A50 includes the glass composition according to any one of the thirty-seventh to forty-ninth aspects A37 to A49, wherein the glass composition is substantially free of MgO, CaO, ZnO, Cl or a combination thereof.
[0058] The fifty-first aspect A51 includes the glass composition of any one of the thirty-seventh to fiftieth aspects A37 to A50, wherein the glass composition comprises greater than or equal to 7 mol % and less than or equal to 18 mol % of Li 2 O.
[0059] The fifty-second aspect A52 includes the glass composition according to the fifty-first aspect A51, wherein the glass composition comprises greater than or equal to 9 mol % and less than or equal to 16 mol % of Li 2 O.
[0060] A fifty-third aspect A53 includes the glass composition of any one of the thirty-seventh to fifty-second aspects A37 to A52, wherein the glass composition comprises greater than or equal to 1 mol % and less than or equal to 12 mol % of Na 2 O.
[0061] The fifty-fourth aspect A54 includes the glass composition according to the fifty-third aspect A53, wherein the glass composition comprises greater than or equal to 2 mol% and less than or equal to 10 mol% of Na 2 O.
[0062] A fifty-fifth aspect A55 includes the glass composition of any one of the thirty-seventh to fifty-fourth aspects A37 to A54, wherein the glass composition comprises greater than or equal to 0.1 mol % and less than or equal to 0.5 mol % of K 2 O.
[0063] A fifty-sixth aspect A56 includes the glass composition of any one of the thirty-seventh to fifty-fifth aspects A37 to A55, wherein the glass composition comprises greater than or equal to 9 mol % and less than or equal to 23 mol % of Al. 2 O 3 .
[0064] The fifty-seventh aspect A57 includes the glass composition according to the fifty-sixth aspect A56, wherein the glass composition comprises greater than or equal to 11 mol % and less than or equal to 20 mol % of Al. 2 O 3 .
[0065] Aspect A58 of the fifty-eighth aspect includes the glass composition of any one of aspects A37 to A57 of the thirty-seventh to fifty-seventh aspects, wherein the glass composition comprises greater than or equal to 2 mol % and less than or equal to 12 mol % of B. 2 O 3 .
[0066] The fifty-ninth aspect A59 includes the glass composition according to the fifty-eighth aspect A58, wherein the glass composition comprises greater than or equal to 3 mol % and less than or equal to 10 mol % of B. 2 O 3 .
[0067] Sixtieth aspect A60 includes the glass composition of any one of thirty-seventh to fifty-ninth aspects A37 to A59, wherein the glass composition comprises greater than or equal to 52 mol % and less than or equal to 75 mol % SiO 2 .
[0068] According to the sixty-first aspect A61, a method of forming a colored glass article may include: heat treating a glass composition to form a glass article, the glass composition comprising: greater than or equal to 50 mol % and less than or equal to 80 mol % of SiO 2 ; greater than or equal to 7 mol% and less than or equal to 25 mol% Al 2 O 3 ; greater than or equal to 1 mol% and less than or equal to 15 mol% B 2 O 3 ; greater than or equal to 5 mol% and less than or equal to 20 mol% Li 2 O; 0.5 mol% or more and 15 mol% or less of Na 2 O; K greater than 0 mol% and less than or equal to 1 mol% 2 O; and greater than or equal to 1×10 -6 mol% and less than or equal to 1 mol% Au, where: R 2 O-Al 2 O 3 Greater than or equal to -5 mol% and less than or equal to 7 mol%, R 2 O is Li 2 O、Na 2 O and K 2 O; and subjecting the glass article to a heat treatment cycle at a temperature greater than or equal to 500° C. and less than or equal to 800° C. and a duration greater than or equal to 0.25 hours and less than or equal to 24 hours to produce the colored glass article.
[0069] According to the second sixty-first aspect A61.1, a method of forming a colored glass article may include: thermally treating a glass composition to form a glass article, the glass composition comprising: greater than or equal to 50 mol % and less than or equal to 80 mol % SiO 2 ; greater than or equal to 7 mol% and less than or equal to 25 mol% Al 2 O 3; greater than or equal to 1 mol% and less than or equal to 15 mol% B 2 O 3 ; greater than or equal to 7 mol% and less than or equal to 20 mol% Li 2 O; 0.5 mol% or more and 12 mol% or less of Na 2 O; K greater than 0 mol% and less than or equal to 1 mol% 2 O; and greater than or equal to 1×10 - 6 mol% and less than or equal to 1 mol% Au, where: R 2 O-Al 2 O 3 Greater than or equal to -5 mol% and less than or equal to 5 mol%, R 2 O is Li 2 O、Na 2 O and K 2 O; and subjecting the glass article to a heat treatment cycle at a temperature greater than or equal to 500° C. and less than or equal to 800° C. and a duration greater than or equal to 0.25 hours and less than or equal to 24 hours to produce the colored glass article.
[0070] Sixty-second aspect A62 includes the method of sixty-first aspect A61 or sixty-first aspect A61.1, wherein the temperature of the heat treatment cycle is greater than or equal to 550°C and less than or equal to 775°C.
[0071] Sixty-third aspect A63 includes the method of any of the sixty-first to sixty-second aspects A61-A62, wherein the duration of the heat treatment cycle is greater than or equal to 0.5 hours and less than or equal to 16 hours.
[0072] The sixty-fourth aspect A64 comprises the method according to any one of the sixty-first to sixty-third aspects A61 to A63, wherein the method further comprises strengthening the colored glass article in an ion exchange bath at a temperature of greater than or equal to 350° C. to less than or equal to 500° C. for a period of time greater than or equal to 2 hours to less than or equal to 12 hours to form an ion-exchanged glass-ceramic article.
[0073] The sixty-fifth aspect A65 includes the method of the sixty-fourth aspect A64, wherein the ion exchange bath comprises KNO 3 .
[0074] The sixty-sixth aspect A66 includes the method according to the sixty-fifth aspect A65, wherein the ion exchange bath comprises NaNO 3 .
[0075] Other features and advantages of the tinted glass articles described herein will be set forth in the detailed description that follows, and in part will be apparent to those skilled in the art from the description, or may be learned by practicing the embodiments described herein, including the detailed description that follows, the claims, and the accompanying drawings.
[0076] It should be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate the various embodiments described herein and together with the description serve to explain the principles and operation of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 is a plan view of an electronic device comprising any tinted glass article according to one or more embodiments described herein;
[0078] Figure 2 yes Figure 1 A perspective view of an electronic device;
[0079] Figure 3 is a colored glass product made of a glass composition and subjected to heat treatment according to one or more embodiments described herein. 2 O-Al 2 O 3 For a*CIELAB space (x-axis: R 2 O-Al 2 O 3 ; Y-axis: a*); and
[0080] Figure 4 A colored glass product R made of a glass composition and subjected to heat treatment according to one or more embodiments described herein 2 O-Al 2 O 3 For b*CIELAB space (x-axis: R 2 O-Al 2 O 3 ; Y-axis: b*). DETAILED DESCRIPTION
[0081] Reference will now be made in detail to various embodiments of glass compositions and colored glass articles formed therefrom having a desired color. According to an embodiment, the colored glass article comprises greater than or equal to 50 mol % and less than or equal to 80 mol % SiO 2 ; greater than or equal to 7 mol% and less than or equal to 25 mol% Al 2O 3 ; greater than or equal to 1 mol% and less than or equal to 15 mol% B 2 O 3 ; greater than or equal to 5 mol% and less than or equal to 20 mol% Li 2 O; 0.5 mol% or more and 15 mol% or less of Na 2 O; K greater than 0 mol% and less than or equal to 1 mol% 2 O; and greater than or equal to 1×10 - 6 mol% and less than or equal to 1 mol% Au. 2 O-Al 2 O 3 Greater than or equal to -5 mol% and less than or equal to 7 mol%, R 2 O is Li 2 O、Na 2 O and K 2 According to an embodiment, the tinted glass article comprises greater than or equal to 50 mol % and less than or equal to 80 mol % of SiO 2 ; greater than or equal to 7 mol% and less than or equal to 25 mol% Al 2 O 3 ; greater than or equal to 1 mol% and less than or equal to 15 mol% B 2 O 3 ; greater than or equal to 7 mol% and less than or equal to 20 mol% Li 2 O; 0.5 mol% or more and 12 mol% or less of Na 2 O; K greater than 0 mol% and less than or equal to 1 mol% 2 O; and greater than or equal to 1×10 -6 mol% and less than or equal to 1 mol% Au. 2 O-Al 2 O 3 Greater than or equal to -5 mol% and less than or equal to 5 mol%, R 2 O is Li 2 O、Na 2 O and K 2 The sum of O.
[0082] Various embodiments of tinted glass articles and methods of making the same will be described herein with specific reference to the accompanying drawings.
[0083] Ranges may be expressed herein as from "about" one particular value, and / or to "about" another particular value. When such a range is expressed, another embodiment includes from a particular value and / or to another particular value. Similarly, when a value is expressed as an approximation by using the antecedent "about," it is understood that the particular value forms another embodiment. It is also understood that the endpoints of each range are significant both in relation to the other endpoint and independently of the other endpoint.
[0084] Directional terms used herein, such as up, down, right, left, front, back, top, and bottom, are only used with reference to the drawings in which they are drawn and do not imply an absolute orientation.
[0085] Unless otherwise expressly stated, any method described herein is in no way intended to be construed as requiring that its steps be performed in a particular order, nor requiring any particular orientation of the apparatus. Thus, in the absence of a method claim actually reciting the order in which its steps are to be followed, or any apparatus claim actually reciting the order or orientation of the individual components, or in the absence of another specific statement in the claim or specification that the steps are to be limited to a particular order, or in the absence of a particular order or orientation of the components of the apparatus, no order or orientation is intended to be inferred in any respect. This applies to any possible non-express basis for interpretation, including: logical issues regarding the arrangement of steps, operational flow, order of components, or orientation of components; ordinary meaning derived from grammatical organization or punctuation, and; the number or type of embodiments described in the specification.
[0086] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a" component includes aspects having two or more such components unless the context clearly dictates otherwise.
[0087] In embodiments of the glass compositions and resulting colored glass articles described herein, the constituent components (e.g., SiO 2 , Al 2 O 3 The concentrations of olefins (such as olefins) are expressed as mole percent (mol%) based on the oxide unless otherwise stated.
[0088] In the embodiments of the glass compositions and resulting colored glass articles described herein, the concentrations of Au and Cl are expressed as mole percent (mol %) unless otherwise indicated.
[0089] When used to describe the concentration and / or absence of a particular constituent component in a glass composition and a resulting tinted glass article, the term "substantially free" means that the constituent component is not intentionally added to the glass composition and the resulting tinted glass article. However, the glass composition and the resulting tinted glass article may contain trace amounts of the constituent component as a contaminant or impurity in an amount less than 0.1 mol%.
[0090] When used to describe the concentration and / or absence of a particular constituent component in a glass composition and resulting tinted glass article, the terms "0 mol %" and "free of" mean that the constituent component is not present in the glass composition and resulting tinted glass article.
[0091] Fracture toughness (K IC ) represents the ability of a glass composition to resist fracture. Fracture toughness is measured on a non-strengthened glass article, for example, K is measured before the glass article is subjected to ion exchange (IOX) treatment. IC The fracture toughness values are thus characteristic of the glass substrate prior to IOX treatment. The fracture toughness test method described herein is not applicable to glass that has been exposed to IOX treatment. However, fracture toughness measurements made on the same glass (e.g., glass substrate) prior to IOX treatment as described herein are correlated to the fracture toughness after IOX treatment and are therefore used as such. The CNSB method is disclosed in Reddy, KPR et al., "Fracture Toughness Measurement of Glass and Ceramic Materials Using Chevron-Notched Specimens," J. Am. Ceram. Soc., 71[6], C-310-C-313 (1988), except that Y* is calculated using Equation 5 of Bubsey, RT et al., "Closed-Form Expressions for Crack-Mouth Displacement and Stress Intensity Factors for Chevron-Notched Short Bar and Short Rod Specimens Based on Experimental Compliance Measurements," NASA Technical Memorandum 83796, pp. 1-30 (October 1992). m .
[0092] As used herein, the term "liquidus viscosity" refers to the viscosity of a glass composition at the onset of devitrification (ie, at the liquidus temperature measured by a gradient furnace method according to ASTM C829-81).
[0093] Surface compressive stress is measured using a surface stress meter (FSM), such as a commercially available instrument such as the FSM-6000 manufactured by Orihara Industrial Co., Ltd. (Japan). Surface stress measurement relies on the measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass article. SOC is in turn measured according to Procedure C (Glass Disk Method) described in ASTM Standard C770-16, entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient," the contents of which are incorporated herein by reference in their entirety. Depth of Compression (DOC) is also measured using a FSM. Maximum Central Tension (CT) values are measured using a Scattered Light Polarizer (SCALP) technique known in the art.
[0094] As used herein, the term "depth of compression" (DOC) refers to the location in an article where compressive stress transitions to tensile stress.
[0095] As used herein, the term "CIELAB color space" refers to a color space defined by the International Commission on Illumination (CIE) in 1976. It expresses color as three values: L* represents lightness from black (0) to white (100), a* represents from green (-) to red (+), and B* represents from blue (-) to yellow (+).
[0096] As used herein, the term "color gamut" refers to the palette of colors achievable by a tinted glass article within the CIELAB color space.
[0097] As used herein, "optical transmission spectra" are obtained using an Agilent Cary 60 spectrophotometer with a scan range of 250 nm to 800 nm, a scan step of 2 nm, a signal average of 0.5 s, and a spot size of 2 mm. The optical transmission data obtained are used to plot coordinates in the CIELAB color space as described in RS Berns, Billmeyer and Saltzman's Principles of Color Technology, 3rd. Ed., John Wiley & Sons, New York (2000).
[0098] Colorants have been added to conventional aluminosilicate glass compositions to obtain colored glass articles having desired colors and improved mechanical properties. For example, glass articles doped with gold (Au) typically appear red, orange, or purple. However, simply including a colorant in an aluminosilicate glass composition may not produce the desired color.
[0099] Disclosed herein are glass compositions and colored glass articles formed therefrom that mitigate the above-mentioned problems, allowing Au to be added to aluminosilicate glass compositions to produce colored glass articles having a desired color while maintaining excellent ion exchange and drop performance. Specifically, the concentrations of certain constituent components can be adjusted to obtain the desired color and prevent precipitation of Au particles in the glass network.
[0100] The glass compositions and tinted glass articles described herein can be described as aluminoborosilicate glass compositions and tinted glass articles, and include SiO 2 、Al 2 O 3 and B 2 O 3 In addition to SiO 2 、Al 2 O 3 and B 2 O 3 In addition, the glass compositions and colored glass articles described herein further include Au to produce colored glass articles having a desired color. The glass compositions and colored glass articles described herein further include alkali metal oxides, such as Li 2 O and Na 2 O to achieve ion exchangeability of the colored glass product. In addition, the R 2 O and Al 2 O 3 The difference (i.e. R 2 O(mol%)-Al 2 O 3 (mol %)) to produce a desired observable color (e.g., pink, purple, red, or orange). In addition, the viscosity of the glass composition can be adjusted to prevent devitrification of the glass composition and precipitation of Au particles during melting and forming, which can limit the achievable color gamut.
[0101] SiO 2 It is the main glass former in the glass composition described herein and can play a role in stabilizing the network structure of the colored glass product. 2 The concentration of SiO should be sufficiently high (e.g., greater than or equal to 50 mol%) to enhance the chemical durability of the glass composition, and, in particular, the resistance of the glass composition to degradation when exposed to acidic solutions, alkaline solutions, and water. 2 The amount of SiO2 (e.g., limited to less than or equal to 80 mol%) is used to control the melting point of the glass composition, because pure SiO2 2 Or high SiO 2 The melting point of glass is undesirably high. Therefore, the SiO 2The concentration of may help improve the meltability and formability of the resulting colored glass article.
[0102] In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 50 mol % and less than or equal to 80 mol % SiO 2 In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 52 mol % and less than or equal to 75 mol % SiO 2 In an embodiment, the SiO in the glass composition and the resulting colored glass product is 2 The concentration of SiO in the glass composition and the colored resulting glass article may be greater than or equal to 50 mol%, greater than or equal to 52 mol%, greater than or equal to 54 mol%, greater than or equal to 56 mol%, greater than or equal to 58 mol%, or even greater than or equal to 60 mol%. 2 The concentration of SiO in the glass composition and the resulting colored glass article may be less than or equal to 80 mol%, less than or equal to 75 mol%, less than or equal to 73 mol%, less than or equal to 71 mol%, or even less than or equal to 69 mol%. 2The concentration of may be greater than or equal to 50 mol% and less than or equal to 80 mol%, greater than or equal to 50 mol% and less than or equal to 75 mol%, greater than or equal to 50 mol% and less than or equal to 73 mol%, greater than or equal to 50 mol% and less than or equal to 71 mol%, greater than or equal to 50 mol% and less than or equal to 69 mol%, greater than or equal to 52 mol% and less than or equal to 80 mol%, greater than or equal to 52 mol% and less than or equal to 75 mol%, greater than or equal to 52 mol% and less than or equal to 73 mol%, greater than or equal to 52 mol% and less than or equal to 71 mol%, greater than or equal to 52 mol% and less than or equal to 69 mol%, greater than or equal to 54 mol% and less than or equal to 80 mol%, greater than or equal to 54 mol% and less than or equal to 75 mol%, greater than or equal to 54 mol% and less than or equal to 73 mol%, greater than or equal to 54 mol% and less than or equal to 71 mol%, greater than or equal to 54 mol% and less than or equal to 69 mol%, greater than or equal to 56 mol% % and less than 80 mol%, greater than or equal to 56 mol% and less than 75 mol%, greater than or equal to 56 mol% and less than 73 mol%, greater than or equal to 56 mol% and less than 71 mol%, greater than or equal to 56 mol% and less than 69 mol%, greater than or equal to 58 mol% and less than 80 mol%, greater than or equal to 58 mol% and less than 75 mol%, greater than or equal to 58 mol% and less than 73 mol%, greater than or equal to 58 mol% and less than 71 mol%, greater than or equal to 58 mol% and less than 69 mol%, greater than or equal to 50 mol% and less than 80 mol%, greater than or equal to 60 mol% and less than 75 mol%, greater than or equal to 60 mol% and less than 73 mol%, greater than or equal to 60 mol% and less than 71 mol%, or even greater than or equal to 60 mol% and less than 69 mol%, or any and all subranges formed by any of these endpoints.
[0103] Like SiO 2 Same, Al 2 O 3 It can also stabilize the glass network and additionally provide improved mechanical properties and chemical durability to the glass composition and the resulting colored glass article. 2 O 3 The amount of Al may be included to control the viscosity of the glass composition. 2 O 3 , so that the obtained glass composition has a desired fracture toughness (for example, greater than or equal to 0.7 MPa·m 1 / 2 ). However, if Al 2 O 3 If the amount of is too high (eg, greater than 25 mol%), the viscosity of the glass melt may increase, thereby reducing the formability of the colored glass article.
[0104] Thus, in embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 7 mol % and less than or equal to 25 mol % Al 2 O 3 In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 9 mol % and less than or equal to 23 mol % Al 2 O 3 In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 11 mol % and less than or equal to 20 mol % Al 2 O 3 In an embodiment, the glass composition and the resulting colored glass product contain Al 2 O 3 The concentration of Al in the glass composition and the resulting colored glass article may be greater than or equal to 7 mol%, greater than or equal to 9 mol%, greater than or equal to 11 mol%, or even greater than or equal to 13 mol%. 2 O 3 The concentration of Al in the glass composition and the resulting colored glass article may be less than or equal to 25 mol%, less than or equal to 23 mol%, less than or equal to 20 mol%, or even less than or equal to 17 mol%. 2 O 3The concentration of may be greater than or equal to 7 mol% and less than or equal to 25 mol%, greater than or equal to 7 mol% and less than or equal to 23 mol%, greater than or equal to 7 mol% and less than or equal to 20 mol%, greater than or equal to 7 mol% and less than or equal to 17 mol%, greater than or equal to 9 mol% and less than or equal to 25 mol%, greater than or equal to 9 mol% and less than or equal to 23 mol%, greater than or equal to 9 mol% and less than or equal to 20 mol%, greater than or equal to 9 mol% and less than or equal to 17 mol%, greater than or equal to 1 ...%. % and less than 25 mol%, greater than or equal to 11 mol% and less than 23 mol%, greater than or equal to 11 mol% and less than 20 mol%, greater than or equal to 11 mol% and less than 17 mol%, greater than or equal to 13 mol% and less than 25 mol%, greater than or equal to 13 mol% and less than 23 mol%, greater than or equal to 13 mol% and less than 20 mol%, greater than or equal to 13 mol% and less than 17 mol%, or any and all subranges formed by any of these endpoints.
[0105] B 2 O 3 It helps to improve the damage resistance of the resulting colored glass product. 2 O 3 Reduce the formation of non-bridging oxygen. The presence of non-bridging oxygen can reduce the fracture toughness. 2 O 3 The concentration of B should be high enough (e.g., greater than or equal to 1 mol%) to lower the melting point of the glass composition, improve formability, and increase the fracture toughness of the colored glass article. 2 O 3 Too high (eg, greater than 15 mol%), and the annealing point and strain point may be reduced, which increases stress relaxation and reduces the overall strength of the tinted glass article.
[0106] In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 1 mol % and less than or equal to 15 mol % of B. 2 O 3 In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 2 mol % and less than or equal to 12 mol % of B 2 O 3 In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 3 mol % and less than or equal to 10 mol % of B 2 O 3 In an embodiment, the glass composition and the resulting colored glass product have B2 O 3 The concentration of B in the glass composition and the resulting colored glass article may be greater than or equal to 1 mol%, greater than or equal to 2 mol%, greater than or equal to 3 mol%, or even greater than or equal to 4 mol%. 2 O 3 The concentration of B in the glass composition and the resulting colored glass article may be less than or equal to 15 mol%, less than or equal to 12 mol%, less than or equal to 10 mol%, less than or equal to 8 mol%, or even less than or equal to 6 mol%. 2 O 3 The concentration of may be greater than or equal to 1 mol% and less than or equal to 15 mol%, greater than or equal to 1 mol% and less than or equal to 12 mol%, greater than or equal to 1 mol% and less than or equal to 10 mol%, greater than or equal to 1 mol% and less than or equal to 8 mol%, greater than or equal to 1 mol% and less than or equal to 6 mol%, greater than or equal to 2 mol% and less than or equal to 15 mol%, greater than or equal to 2 mol% and less than or equal to 12 mol%, greater than or equal to 2 mol% and less than or equal to 10 mol%, greater than or equal to 2 mol% and less than or equal to 8 mol%, greater than or equal to 2 mol% and less than or equal to 6 mol%, greater than or equal to 3 mol% and less than or equal to 15 mol%, greater than or equal to 3 mol% and less than or equal to 12 mol%, greater than or equal to 3 mol% and less than or equal to 10 mol%, greater than or equal to 3 mol% and less than or equal to 8 mol%, greater than or equal to 3 mol% and less than or equal to 6 mol%, greater than or equal to 4 mol% and less than or equal to 15 mol%, greater than or equal to 4 mol% and less than or equal to 12 mol%, greater than or equal to 4 mol% and less than or equal to 10 mol%, greater than or equal to 4 mol% and less than or equal to 8 mol%, or even greater than or equal to 4 mol% and less than or equal to 6 mol%, or any and all subranges formed by any of these endpoints.
[0107] As described above, the glass composition and the resulting colored glass article may include alkali metal oxides, such as Li 2 O、Na 2 O and K 2 O, to achieve ion exchangeability of colored glass products.
[0108] Li 2 O contributes to the ion exchange capacity of the colored glass product and also lowers the softening point of the glass composition, thereby improving the formability of the colored glass product. 2 O lowers the melting point of the glass composition, which helps improve Au retention. 2The concentration of O in the glass composition and the resulting colored glass article should be high enough (e.g., greater than or equal to 5 mol%) to reduce the melting point of the glass composition and achieve a desired maximum central tension (e.g., greater than or equal to 40 MPa) after ion exchange. 2 If the amount of O is too high (eg, greater than 20 mol%), the liquidus temperature may increase, thereby reducing the manufacturability of the colored glass article.
[0109] In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 5 mol % and less than or equal to 20 mol % of Li 2 O or 7 mol% or more and 20 mol% or less of Li 2 In embodiments, the glass composition and resulting colored glass article may include greater than or equal to 7 mol % and less than or equal to 18 mol % of Li 2 In embodiments, the glass composition and resulting colored glass article may include greater than or equal to 9 mol % and less than or equal to 16 mol % of Li 2 In embodiments, Li in the glass composition and the resulting colored glass product 2 The concentration of O may be greater than or equal to 5 mol%, greater than or equal to 7 mol%, or even greater than or equal to 9 mol%. In embodiments, the Li 2 The concentration of O may be less than or equal to 20 mol%, less than or equal to 18 mol%, less than or equal to 16 mol%, less than or equal to 14 mol%, or even less than or equal to 12 mol%. In embodiments, the Li in the glass composition and the resulting colored glass article 2The concentration of O can be greater than or equal to 5 mol% and less than or equal to 20 mol%, greater than or equal to 5 mol% and less than or equal to 18 mol%, greater than or equal to 5 mol% and less than or equal to 16 mol%, greater than or equal to 5 mol% and less than or equal to 14 mol%, greater than or equal to 5 mol% and less than or equal to 12 mol%, greater than or equal to 7 mol% and less than or equal to 20 mol%, greater than or equal to 7 mol% and less than or equal to 18 mol%, greater than or equal to 7 mol% and less than or equal to 16 mol%, greater than or equal to 7 mol% and less than or equal to 14 mol%, greater than or equal to 7 mol% and less than or equal to 12 mol%, greater than or equal to 9 mol% and less than or equal to 20 mol%, greater than or equal to 9 mol% and less than or equal to 18 mol%, greater than or equal to 9 mol% and less than or equal to 16 mol%, greater than or equal to 9 mol% and less than or equal to 14 mol%, or even greater than or equal to 9 mol% and less than or equal to 12 mol%, or any and all subranges formed by any of these endpoints.
[0110] Na 2 O improves the diffusion rate of alkali ions in the glass, thereby reducing the ion exchange time and helping to obtain a desired surface compressive stress (e.g., greater than or equal to 300 MPa). Na 2 O also improves the formability of colored glass products. However, if too much Na is added to the glass composition 2 O, the melting point may be too low. Therefore, in embodiments, the Li present in the glass composition and the resulting colored glass article 2 The concentration of O may be greater than the Na present in the glass composition and the resulting colored glass article. 2 The concentration of O.
[0111] In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 0.5 mol % and less than or equal to 15 mol % of Na 2 O or greater than or equal to 0.5 mol % and less than or equal to 12 mol % of Na 2 In embodiments, the glass composition and resulting colored glass article may include greater than or equal to 1 mol % and less than or equal to 12 mol % of Na 2 In embodiments, the glass composition and resulting colored glass article may include greater than or equal to 2 mol % and less than or equal to 10 mol % of Na 2 In embodiments, Na in the glass composition and the resulting colored glass product is 2The concentration of O may be greater than or equal to 0.5 mol%, greater than or equal to 1 mol%, greater than or equal to 2 mol%, greater than or equal to 3 mol%, or even greater than or equal to 4 mol%. In embodiments, Na in the glass composition and the resulting colored glass article 2 The concentration of O may be less than or equal to 15 mol%, less than or equal to 12 mol%, less than or equal to 10 mol%, less than or equal to 8 mol%, or even less than or equal to 6 mol%. In embodiments, Na in the glass composition and the resulting colored glass article 2 The concentration of O may be greater than or equal to 0.5 mol% and less than or equal to 15 mol%, greater than or equal to 0.5 mol% and less than or equal to 12 mol%, greater than or equal to 0.5 mol% and less than or equal to 10 mol%, greater than or equal to 0.5 mol% and less than or equal to 8 mol%, greater than or equal to 0.5 mol% and less than or equal to 6 mol%, greater than or equal to 1 mol% and less than or equal to 15 mol%, greater than or equal to 1 mol% and less than or equal to 12 mol%, greater than or equal to 1 mol% and less than or equal to 10 mol%, greater than or equal to 1 mol% and less than or equal to 8 mol%, greater than or equal to 1 mol% and less than or equal to 6 mol%, greater than or equal to 2 mol% and less than or equal to 15 mol%, greater than or equal to 2 mol% and less than or equal to 12 mol%, greater than or equal to 2 mol% and less than or equal to % and less than 15 mol%, greater than or equal to 3 mol% and less than 12 mol%, greater than or equal to 3 mol% and less than 10 mol%, greater than or equal to 3 mol% and less than 8 mol%, greater than or equal to 3 mol% and less than 6 mol%, greater than or equal to 4 mol% and less than 15 mol%, greater than or equal to 4 mol% and less than 12 mol%, greater than or equal to 4 mol% and less than 10 mol%, greater than or equal to 4 mol% and less than 8 mol%, or even greater than or equal to 4 mol% and less than 6 mol%, or any and all subranges formed by any of these endpoints.
[0112] K 2 O promotes ion exchange and can increase compression depth and lower melting point to improve the formability of colored glass products. However, adding too much K 2 O may cause surface compressive stress and a too low melting point. Therefore, in an embodiment, K added to the glass composition 2 The amount of O may be limited.
[0113] In embodiments, the glass composition and resulting tinted glass article may include greater than 0 mol % and less than or equal to 1 mol % of K 2 In embodiments, the glass composition and resulting colored glass article may optionally include greater than 0.1 mol % and less than or equal to 0.5 mol % of K 2 In embodiments, the glass composition and the resulting colored glass product contain K 2 The concentration of O may be greater than 0 mol% or even greater than or equal to 0.1 mol%. In embodiments, K in the glass composition and the resulting colored glass article 2 The concentration of O may be less than or equal to 1 mol%, less than or equal to 0.5 mol%, or even less than or equal to 0.25 mol%. In embodiments, the K in the glass composition and the resulting colored glass article 2 The O concentration can be greater than 0 mol% and less than or equal to 1 mol%, greater than 0 mol% and less than or equal to 0.5 mol%, greater than 0 mol% and less than or equal to 0.25 mol%, greater than or equal to 0.1 mol% and less than or equal to 1 mol%, greater than or equal to 0.1 mol% and less than or equal to 0.5 mol%, or even greater than or equal to 0.1 mol% and less than or equal to 0.25 mol%, or any and all subranges formed by any of these endpoints.
[0114] As used herein, R 2 O is present in the glass composition of Na 2 O.K 2 O and Li 2 The total amount of O (in mol%) (i.e., R 2 O=Na 2 O(mol%)+K 2 O(mol%)+Li 2 As described herein, alkali metal oxides such as Na 2 O.K 2 O and Li 2 O helps to lower the softening point and molding temperature of the glass composition, thereby offsetting the 2 The softening point and molding temperature of the glass composition are increased due to a higher amount of alkali metal oxide. The reduction in softening point and molding temperature can be further reduced by including a combination of alkali metal oxides (e.g., two or more alkali metal oxides) in the glass composition, a phenomenon known as the "mixed alkali metal effect". However, it has been found that if the amount of alkali metal oxide is too high, the average thermal expansion coefficient of the glass composition increases to more than 100×10 -7 / ℃, which may not be desirable.
[0115] In embodiments, the glass composition and the resulting colored glass article have R 2 The concentration of O may be greater than or equal to 6 mol% and less than or equal to 25 mol%. In embodiments, R 2 The concentration of O may be greater than or equal to 8 mol% and less than or equal to 23 mol%. In embodiments, R 2 The concentration of O may be greater than or equal to 6 mol%, greater than or equal to 8 mol%, greater than or equal to 10 mol%, greater than or equal to 12 mol%, or even greater than or equal to 14 mol%. In embodiments, R 2 The concentration of O may be less than or equal to 25 mol%, less than or equal to 23 mol%, less than or equal to 20 mol%, or even less than or equal to 18 mol%. In embodiments, R 2 The concentration of O may be greater than or equal to 6 mol% and less than or equal to 25 mol%, greater than or equal to 6 mol% and less than or equal to 23 mol%, greater than or equal to 6 mol% and less than or equal to 20 mol%, greater than or equal to 6 mol% and less than or equal to 18 mol%, greater than or equal to 8 mol% and less than or equal to 25 mol%, greater than or equal to 8 mol% and less than or equal to 23 mol%, greater than or equal to 8 mol% and less than or equal to 20 mol%, greater than or equal to 8 mol% and less than or equal to 18 mol%, greater than or equal to 10 mol% and less than or equal to 25 mol%, greater than or equal to 10 mol% and less than or equal to 23 mol%, greater than or equal to 10 mol% and less than or equal to 20 mol%, greater than or equal to 10 mol% and less than or equal to 18 mol%, greater than or equal to 12 mol% and less than or equal to 25 mol%, greater than or equal to 12 mol% and less than or equal to 23 mol%, greater than or equal to 12 mol% and less than or equal to 20 mol%, greater than or equal to 12 mol% and less than or equal to 18 mol%, greater than or equal to 14 mol% and less than or equal to 25 mol%, greater than or equal to 14 mol% and less than or equal to 23 mol%, greater than or equal to 14 mol% and less than or equal to 20 mol%, or even greater than or equal to 14 mol% and less than or equal to 18 mol%, or any and all subranges formed by any of these endpoints.
[0116] In an embodiment, the R in the glass composition can be adjusted 2 O and Al 2 O 3 The difference between 2 O(mol%)-Al 2 O3 (mol%)) to produce the desired observable color (e.g., pink, purple, red, or orange). Together with the temperature and time of the heat treatment, the R 2 O-Al 2 O 3 can be associated with the observable color of the colored glass article after heat treatment, as described herein. In embodiments, R in the glass composition and the resulting colored glass article 2 O-Al 2 O 3 It may be greater than or equal to -5 mol% and less than or equal to 7 mol%, or greater than or equal to -5 mol% and less than or equal to 5 mol%. In an embodiment, R in the glass composition and the resulting colored glass product 2 O-Al 2 O 3 It may be greater than or equal to -3 mol% and less than or equal to 6 mol%. In an embodiment, R in the glass composition and the resulting colored glass product 2 O-Al 2 O 3 It may be greater than or equal to -1 mol% and less than or equal to 5 mol%. In an embodiment, R in the glass composition and the resulting colored glass product 2 O-Al 2 O 3 It may be greater than or equal to -5 mol% and less than or equal to 1.5 mol%. In an embodiment, R in the glass composition and the resulting colored glass product 2 O-Al 2 O 3 It may be greater than or equal to -3 mol% and less than or equal to 1.5 mol%. In an embodiment, R in the glass composition and the resulting colored glass product 2 O-Al 2 O 3 It may be greater than or equal to 1.5 mol% and less than or equal to 7 mol%. In an embodiment, R in the glass composition and the resulting colored glass product 2 O-Al 2 O 3 It may be greater than or equal to 1.5 mol% and less than or equal to 5 mol%. In an embodiment, R in the glass composition and the resulting colored glass product 2 O-Al 2 O 3 It may be greater than or equal to -5 mol%, greater than or equal to -3, greater than or equal to -1 mol%, greater than or equal to 0 mol%, or even greater than or equal to 1.5. In embodiments, R in the glass composition and the resulting colored glass article 2 O-Al2 O 3 The R in the glass composition and the resulting colored glass article may be less than or equal to 7 mol%, less than or equal to 5 mol%, less than or equal to 3 mol%, or even less than or equal to 1.5 mol%. 2 O-Al 2 O 3 It may be greater than or equal to -5 mol% and less than or equal to 7 mol%, greater than or equal to -5 mol% and less than or equal to 5 mol%, greater than or equal to -5 mol% and less than or equal to 3 mol%, greater than or equal to -5 mol% and less than or equal to 1.5 mol%, greater than or equal to -3 mol% and less than or equal to 7 mol%, greater than or equal to -3 mol% and less than or equal to 5 mol%, greater than or equal to -3 mol% and less than or equal to 3 mol%, greater than or equal to -3 mol% and less than or equal to 1.5 mol%, greater than or equal to -1 mol% and less than or equal to 7 mol%, greater than or equal to -1 mol% and less than or equal to 5 mol%, Greater than or equal to -1 mol% and less than or equal to 3 mol%, greater than or equal to -1 mol% and less than or equal to 1.5 mol%, greater than or equal to 0 mol% and less than or equal to 7 mol%, greater than or equal to 0 mol% and less than or equal to 5 mol%, greater than or equal to 0 mol% and less than or equal to 3 mol%, greater than or equal to 0 mol% and less than or equal to 1.5 mol%, greater than or equal to 1.5 mol% and less than or equal to 7 mol%, greater than or equal to 1.5 mol% and less than or equal to 5 mol%, or even greater than or equal to 1.5 mol% and less than or equal to 3 mol%, or any and all subranges formed by any of these endpoints.
[0117] The glass compositions and resulting colored glass articles described herein may also include ZrO 2 In addition to Au, ZrO 2 It can also be used as a colorant to produce, for example, red colored glass products. In an embodiment, the glass composition and the resulting colored glass product may include greater than or equal to 0.01 mol % and less than or equal to 2 mol % of ZrO. 2 In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 0.1 mol % and less than or equal to 1.5 mol % ZrO 2 In an embodiment, the glass composition contains ZrO 2 The concentration of ZrO may be greater than or equal to 0 mol%, greater than or equal to 0.01 mol%, greater than or equal to 0.1 mol%, or even greater than or equal to 0.2 mol%. In an embodiment, the glass composition contains ZrO 2The concentration of ZrO may be less than or equal to 2 mol%, less than or equal to 1.5 mol%, less than or equal to 1 mol%, less than or equal to 0.75 mol%, or even less than or equal to 0.5 mol%. In an embodiment, the glass composition contains ZrO 2 The concentration of may be greater than or equal to 0 mol% and less than or equal to 2 mol%, greater than or equal to 0 mol% and less than or equal to 1.5 mol%, greater than or equal to 0 mol% and less than or equal to 1 mol%, greater than or equal to 0 mol% and less than or equal to 0.75 mol%, greater than or equal to 0 mol% and less than or equal to 0.5 mol%, greater than or equal to 0.01 mol% and less than or equal to 2 mol%, greater than or equal to 0.01 mol% and less than or equal to 1.5 mol%, greater than or equal to 0.01 mol% and less than or equal to 1 mol%, greater than or equal to 0.01 mol% and less than or equal to 0.75 mol%, greater than or equal to 0.01 mol% and less than or equal to 0.5 mol%, greater than or equal to 0.1 mol% and less than or equal to % and less than 1 mol%, 0.1 mol% and less than 1.5 mol%, 0.1 mol% and less than 1 mol%, 0.1 mol% and less than 0.75 mol%, 0.1 mol% and less than 0.5 mol%, 0.2 mol% and less than 2 mol%, 0.2 mol% and less than 1.5 mol%, 0.2 mol% and less than 1 mol%, 0.2 mol% and less than 0.75 mol%, or even 0.2 mol% and less than 0.5 mol%, or any and all subranges formed by any of these endpoints. In embodiments, the glass composition and the resulting tinted glass article may be substantially free of or free of ZrO. 2 .
[0118] The glass compositions and resulting colored glass articles described herein may also include Fe 2 O 3 In addition to Au, Fe 2 O 3 It can also act as a colorant, producing a colored glass article that can be, for example, pink or red. In an embodiment, the glass composition and the resulting colored glass article can include greater than or equal to 0.01 mol % and less than or equal to 1 mol % of Fe 2 O 3 In embodiments, the glass composition and resulting tinted glass article may include greater than or equal to 0.05 mol % and less than or equal to 1 mol % of Fe 2 O 3 In an embodiment, the glass composition has Fe2 O 3 The concentration of Fe may be greater than or equal to 0 mol%, greater than or equal to 0.01 mol%, or even greater than or equal to 0.05 mol%. In an embodiment, the glass composition has Fe 2 O 3 The concentration of Fe may be less than or equal to 1 mol%, less than or equal to 0.75 mol%, less than or equal to 0.5 mol%, or even less than or equal to 0.25 mol%. In an embodiment, the glass composition has Fe 2 O 3 The concentration of Fe may be greater than or equal to 0 mol% and less than or equal to 1 mol%, greater than or equal to 0 mol% and less than or equal to 0.75 mol%, greater than or equal to 0 mol% and less than or equal to 0.5 mol%, greater than or equal to 0 mol% and less than or equal to 0.25 mol%, greater than or equal to 0.01 mol% and less than or equal to 1 mol%, greater than or equal to 0.01 mol% and less than or equal to 0.75 mol%, greater than or equal to 0.01 mol% and less than or equal to 0.5 mol%, greater than or equal to 0.01 mol% and less than or equal to 0.25 mol%, greater than or equal to 0.05 mol% and less than or equal to 1 mol%, greater than or equal to 0.05 mol% and less than or equal to 0.75 mol%, greater than or equal to 0.05 mol% and less than or equal to 0.5 mol%, or even greater than or equal to 0.05 mol% and less than or equal to 0.25 mol%, or any and all subranges formed by any of these endpoints. In embodiments, the glass composition and the resulting tinted glass article may be substantially free of or free of Fe. 2 O 3 .
[0119] The glass compositions and resulting colored glass articles described herein may also include one or more fining agents. In embodiments, the fining agent may include, for example, SnO 2 In embodiments, the glass composition and resulting colored glass article may include greater than or equal to 0.01 mol % and less than or equal to 1 mol % SnO 2 In embodiments, the glass composition and resulting colored glass article may include greater than or equal to 0.05 mol % and less than or equal to 0.75 mol % SnO 2 In an embodiment, the glass composition contains SnO 2 The concentration of SnO may be greater than or equal to 0 mol%, greater than or equal to 0.01 mol%, or greater than or equal to 0.05 mol%. In an embodiment, the SnO 2The concentration of SnO may be less than or equal to 1 mol%, less than or equal to 0.75 mol%, less than or equal to 0.5 mol%, or even less than or equal to 0.25 mol%. In an embodiment, the SnO in the glass composition 2 The concentration of SnO can be greater than or equal to 0 mol% and less than or equal to 1 mol%, greater than or equal to 0 mol% and less than or equal to 0.75 mol%, greater than or equal to 0 mol% and less than or equal to 0.5 mol%, greater than or equal to 0 mol% and less than or equal to 0.25 mol%, greater than or equal to 0.01 mol% and less than or equal to 1 mol%, greater than or equal to 0.01 mol% and less than or equal to 0.75 mol%, greater than or equal to 0.01 mol% and less than or equal to 0.5 mol%, greater than or equal to 0.01 mol% and less than or equal to 0.25 mol%, greater than or equal to 0.05 mol% and less than or equal to 1 mol%, greater than or equal to 0.05 mol% and less than or equal to 0.75 mol%, greater than or equal to 0.05 mol% and less than or equal to 0.5 mol%, or even greater than or equal to 0.01 mol% and less than or equal to 0.25 mol%, or any and all subranges formed by any of these endpoints. In embodiments, the glass composition and the resulting colored glass article may be substantially free of or free of SnO. 2 .
[0120] In embodiments, the glass compositions and resulting tinted glass articles may include alkaline earth metal oxides such as MgO, ZnO, CaO, SrO, and BaO.
[0121] In an embodiment, the concentration of MgO in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% or even greater than or equal to 0.5 mol%. In an embodiment, the concentration of MgO in the glass composition and the resulting colored glass article may be less than or equal to 2 mol% or even less than or equal to 1 mol%. In an embodiment, the concentration of MgO in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% and less than or equal to 2 mol%, greater than or equal to 0 mol% and less than or equal to 1 mol%, greater than or equal to 0.5 mol% and less than or equal to 2 mol%, or even greater than or equal to 0.5 mol% and less than or equal to 1 mol%, or any and all subranges formed by any of these endpoints. In an embodiment, the glass composition and the resulting colored glass article may be substantially free of or free of MgO.
[0122] In an embodiment, the concentration of ZnO in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% or even greater than or equal to 0.5 mol%. In an embodiment, the concentration of ZnO in the glass composition and the resulting colored glass article may be less than or equal to 2 mol% or even less than or equal to 1 mol%. In an embodiment, the concentration of ZnO in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% and less than or equal to 2 mol%, greater than or equal to 0 mol% and less than or equal to 1 mol%, greater than or equal to 0.5 mol% and less than or equal to 2 mol%, or even greater than or equal to 0.5 mol% and less than or equal to 1 mol%, or any and all subranges formed by any of these endpoints. In an embodiment, the glass composition and the resulting colored glass article may be substantially free of or free of ZnO.
[0123] In an embodiment, the concentration of CaO in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% or even greater than or equal to 0.5 mol%. In an embodiment, the concentration of CaO in the glass composition and the resulting colored glass article may be less than or equal to 2 mol% or even less than or equal to 1 mol%. In an embodiment, the concentration of CaO in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% and less than or equal to 2 mol%, greater than or equal to 0 mol% and less than or equal to 1 mol%, greater than or equal to 0.5 mol% and less than or equal to 2 mol%, or even greater than or equal to 0.5 mol% and less than or equal to 1 mol%, or any and all subranges formed by any of these endpoints. In an embodiment, the glass composition and the resulting colored glass article may be substantially free or free of CaO.
[0124] In an embodiment, the concentration of SrO in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% or even greater than or equal to 0.5 mol%. In an embodiment, the concentration of SrO in the glass composition and the resulting colored glass article may be less than or equal to 2 mol% or even less than or equal to 1 mol%. In an embodiment, the concentration of SrO in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% and less than or equal to 2 mol%, greater than or equal to 0 mol% and less than or equal to 1 mol%, greater than or equal to 0.5 mol% and less than or equal to 2 mol%, or even greater than or equal to 0.5 mol% and less than or equal to 1 mol%, or any and all subranges formed by any of these endpoints. In an embodiment, the glass composition and the resulting colored glass article may be substantially free of or free of SrO.
[0125] In an embodiment, the concentration of BaO in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% or even greater than or equal to 0.5 mol%. In an embodiment, the concentration of BaO in the glass composition and the resulting colored glass article may be less than or equal to 2 mol% or even less than or equal to 1 mol%. In an embodiment, the concentration of BaO in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% and less than or equal to 2 mol%, greater than or equal to 0 mol% and less than or equal to 1 mol%, greater than or equal to 0.5 mol% and less than or equal to 2 mol%, or even greater than or equal to 0.5 mol% and less than or equal to 1 mol%, or any and all subranges formed by any of these endpoints. In an embodiment, the glass composition and the resulting colored glass article may be substantially free of or free of BaO.
[0126] In an embodiment, the glass composition and the resulting colored glass article may include Cl, which may allow specific Au particles to grow. In an embodiment, the concentration of Cl in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% or even greater than or equal to 0.1 mol%. In an embodiment, the concentration of Cl in the glass composition and the resulting colored glass article may be less than or equal to 0.5 mol%, or even less than or equal to 0.25 mol%. In an embodiment, the concentration of Cl in the glass composition and the resulting colored glass article may be greater than or equal to 0 mol% and less than or equal to 0.5 mol%, greater than or equal to 0 mol% and less than or equal to 0.25 mol%, greater than or equal to 0.1 mol% and less than or equal to 0.5 mol%, or even greater than or equal to 0.1 mol% and less than or equal to 0.25 mol%, or any and all subranges formed by any of these endpoints. In an embodiment, the glass composition and the resulting colored glass article may be substantially free of or free of Cl.
[0127] In embodiments, the glass compositions and resulting tinted glass articles may be substantially free or free of MgO, CaO, ZnO, Cl, or combinations thereof.
[0128] The glass compositions and resulting colored glass articles described herein also include Au as a colorant to achieve a desired color. In an embodiment, the glass compositions and resulting colored glass articles may include greater than or equal to 1×10 -6 mol% and less than or equal to 1 mol% Au. In embodiments, the glass composition and the resulting colored glass article may include greater than or equal to 0.0001 mol% and less than or equal to 0.1 mol% Au. In embodiments, the concentration of Au in the glass composition and the resulting colored glass article may be greater than or equal to 1×10 -6 mol%, greater than or equal to 1×10-5 mol%, greater than or equal to 0.0001 mol%, greater than or equal to 0.0005 mol%, or even greater than or equal to 0.001 mol%. In embodiments, the concentration of Au in the glass composition and the resulting colored glass article may be less than or equal to 1 mol%, less than or equal to 0.75 mol%, less than or equal to 0.5 mol%, less than or equal to 0.25 mol%, less than or equal to 0.1 mol%, less than or equal to 0.05 mol%, or even less than or equal to 0.01. In embodiments, the concentration of Au in the glass composition and the resulting colored glass article may be greater than or equal to 1×10 -6 mol% and less than or equal to 0.75mol%, greater than or equal to 1x10 -6 mol% and less than or equal to 0.5mol%, greater than or equal to 1x10 -6 mol% and less than or equal to 0.25mol%, greater than or equal to 1x10 - 6 mol% and less than or equal to 0.1mol%, greater than or equal to 1x10 -6 mol% and less than or equal to 0.05mol%, greater than or equal to 1x10 -6 mol% and less than or equal to 0.01mol%, greater than or equal to 1x10 -5 mol% and less than or equal to 1mol%, greater than or equal to 1x10 -5 mol% and less than or equal to 0.75mol%, greater than or equal to 1x10 -5 mol% and less than or equal to 0.5mol%, greater than or equal to 1x10 -5 mol% and less than or equal to 0.25mol%, greater than or equal to 1x10 -5 mol% and less than or equal to 0.1mol%, greater than or equal to 1x10 -5 mol% and less than or equal to 0.05mol%, greater than or equal to 1x10 - 5mol% and less than or equal to 0.01mol%, greater than or equal to 0.0001mol% and less than or equal to 1mol%, greater than or equal to 0.0001mol% and less than or equal to 0.75mol%, greater than or equal to 0.0001mol% and less than or equal to 0.5mol%, greater than or equal to 0.0001mol% and less than or equal to 0.25mol%, greater than or equal to 0.0001mol% and less than or equal to 0.1mol%, greater than or equal to 0.0001mol% and less than or equal to 0.05mol%, greater than or equal to 0.0001mol% and less than or equal to 0.01mol%, greater than or equal to 0.0005mol% and less than or equal to 1mol%, greater than or equal to 0.0005mol% and less than or equal to 0.75mol%, greater than or equal to 0.0005mol% and less than or equal to 0.5mol%, greater than or equal to 0.0005mol% and less than or equal to % and less than or equal to 0.25 mol%, greater than or equal to 0.0005 mol% and less than or equal to 0.1 mol%, greater than or equal to 0.0005 mol% and less than or equal to 0.05 mol%, greater than or equal to 0.0005 mol% and less than or equal to 0.01 mol%, greater than or equal to 0.001 mol% and less than or equal to 1 mol%, greater than or equal to 0.001 mol% and less than or equal to 0.75 mol%, greater than or equal to 0.001 mol% and less than or equal to 0.5 mol%, greater than or equal to 0.001 mol% and less than or equal to 0.25 mol%, greater than or equal to 0.001 mol% and less than or equal to 0.1 mol%, greater than or equal to 0.001 mol% and less than or equal to 0.05 mol%, or even greater than or equal to 0.001 mol% and less than or equal to 0.01 mol%, or any and all subranges formed by any of these endpoints.
[0129] In embodiments, the glass compositions and resulting colored glass articles described herein may also include foreign impurities, such as TiO 2 、MnO 2 、MoO 3 , WO 3 , Y 2 O 3 , CdO, As 2 O 3 , sulfur-based compounds such as sulfates, halogens, or combinations thereof. In embodiments, the glass composition and the resulting colored glass article may be substantially free of or free of foreign impurities such as TiO 2 、MnO 2 、MoO 3 , WO 3 , Y 2 O 3, CdO, As 2 O 3 , sulfur-based compounds such as sulfates, halogens, or combinations thereof. In embodiments, an antimicrobial component, a chemical fining agent, or other additional components may be included in the glass composition and the resulting colored glass product.
[0130] In embodiments, the viscosity of the glass composition can be adjusted to prevent devitrification of the glass composition and the formation of Au particles during melting and forming. The formation of Au particles prior to melting can limit the color range that can be achieved by heat treatment. Therefore, in embodiments, in order to achieve the desired viscosity and thereby prevent the formation of Au particles prior to melting, the glass compositions and resulting glass articles described herein can satisfy the following relationship: 5.72*Al 2 O 3 (mol%)-21.4*ZnO(mol%)-2.5*P 2 O 5 (mol%)-35*Li 2 O(mol%)-16.6*B 2 O 3 (mol%)-20.5*MgO (mol%)-23.3*Na 2 O(mol%)-27.9*SrO(mol%)-18.5*K 2 O (mol%) -26.3*CaO (mol%) greater than -609mol%. In embodiments, the glass compositions and resulting glass articles described herein may satisfy the following relationship: 5.72*Al 2 O 3 (mol%)-21.4*ZnO(mol%)-2.5*P 2 O 5 (mol%)-35*Li 2 O(mol%)-16.6*B 2 O 3 (mol%)-20.5*MgO (mol%)-23.3*Na 2 O(mol%)-27.9*SrO(mol%)-18.5*K 2 O (mol%) -26.3 * CaO (mol%) greater than -609 mol%, greater than or equal to -575 mol%, greater than or equal to -550 mol%, or even greater than or equal to -525 mol%. In embodiments, the glass compositions and resulting glass articles described herein may satisfy the following relationship: 5.72 * Al 2 O 3 (mol%)-21.4*ZnO(mol%)-2.5*P 2 O 5(mol%)-35*Li 2 O(mol%)-16.6*B 2 O 3 (mol%)-20.5*MgO (mol%)-23.3*Na 2 O(mol%)-27.9*SrO(mol%)-18.5*K 2 O (mol%) -26.3 * CaO (mol%) is less than or equal to -400 mol%, less than or equal to -425 mol%, or even less than or equal to -450 mol%. In embodiments, the glass compositions and resulting glass articles described herein may satisfy the following relationship: 5.72 * Al 2 O 3 (mol%)-21.4*ZnO(mol%)-2.5*P 2 O 5 (mol%)-35*Li 2 O(mol%)-16.6*B 2 O 3 (mol%)-20.5*MgO (mol%)-23.3*Na 2 O (mol%) -27.9*SrO (mol%) -26.3*CaO (mol%) greater than -609mol% and less than or equal to -400mol%, greater than -609mol% and less than or equal to -425mol%, greater than -609mol% and less than or equal to -450mol%, greater than or equal to -575mol% and less than or equal to -400mol%, greater than or equal to -575mol% and less than or equal to -425mol%, greater than or equal to -575mol% and less than or equal to -450mol% , greater than or equal to -550 mol% and less than or equal to -400 mol%, greater than or equal to -550 mol% and less than or equal to -425 mol%, greater than or equal to -550 mol% and less than or equal to -450 mol%, greater than or equal to -525 mol% and less than or equal to -400 mol%, greater than or equal to -525 mol% and less than or equal to -425 mol%, or even greater than or equal to -525 mol% and less than or equal to -450 mol%, or any and all subranges formed by any of these endpoints.
[0131] In an embodiment, a method of making a glass article comprises heat treating a glass composition described herein at one or more preselected temperatures for one or more preselected times to cause glass homogenization. In an embodiment, the heat treatment for preparing a glass article may comprise (i) heating the glass composition to a glass homogenization temperature at a rate of 1-100°C / min; (ii) maintaining the glass composition at the glass homogenization temperature for a time greater than or equal to 0.25 hours and less than or equal to 4 hours to prepare the glass article; and (iii) cooling the formed glass article to room temperature. In an embodiment, the glass homogenization temperature may be greater than or equal to 300°C and less than or equal to 700°C.
[0132] The glass composition described herein comprises Au, R 2 O and Al 2 O 3 . You can adjust R 2 O and Al 2 O 3 concentration, making different R 2 O-Al 2 O 3 Combining with Au produces a tinted glass article having a desired color (e.g., pink, purple, red, or orange). In an embodiment, the tinted glass article may have a transmittance color coordinate in the CIELAB color space measured under F2 illumination with an article thickness of 1.33 mm and a standard observation angle of 10°: L* greater than or equal to 50 and less than or equal to 100; a* greater than or equal to -15 and less than or equal to 25; and b* greater than or equal to -25 and less than or equal to 25.
[0133] Relatively small concentrations of R 2 O-Al 2 O 3 (e.g., less than or equal to 1.5 mol%) can produce blue or purple glass products. 2 O / Al 2 O 3 (eg, greater than 1.5 mol%) may produce orange or red glass products.
[0134] For example, in an embodiment, R 2 O-Al 2 O 3 may be greater than or equal to -5 mol% and less than or equal to 1.5 mol% and b* may be greater than or equal to -25 and less than or equal to 10. In an embodiment, R 2 O-Al 2 O 3may be greater than or equal to -3 mol% and less than or equal to 1.5 mol% and b* may be greater than or equal to -15 and less than or equal to 7. In an embodiment, R 2 O-Al 2 O 3 can be greater than or equal to -5 mol% and less than or equal to 1.5 mol%, greater than or equal to -3 mol% and less than or equal to 1.5 mol%, greater than or equal to -1 mol% and less than or equal to 1.5 mol%, or even greater than or equal to 0 mol% and less than or equal to 1.5 mol%, or any and all subranges formed by any of these endpoints; and b* can be greater than or equal to -25 and less than or equal to 10, greater than or equal to -25 and less than or equal to 7, greater than or equal to -25 and less than or equal to 5, greater than or equal to -15 and less than or equal to 10, greater than or equal to -15 and less than or equal to 7, greater than or equal to -15 and less than or equal to 5, greater than or equal to -10 and less than or equal to 10, greater than or equal to -10 and less than or equal to 7, or even greater than or equal to -10 and less than or equal to 5, or any and all subranges formed by any of these endpoints.
[0135] In an embodiment, R 2 O-Al 2 O 3 may be greater than 1.5 mol% and less than or equal to 7 mol%, and b* may be greater than or equal to 0 and less than or equal to 25. In an embodiment, R 2 O-Al 2 O 3 may be greater than 1.5 mol% and less than or equal to 5 mol%, and b* may be greater than or equal to 0 and less than or equal to 15. In an embodiment, R 2 O-Al 2 O 3 can be greater than 1.5 mol% and less than or equal to 7 mol%, greater than 1.5 mol% and less than or equal to 5 mol%, or even greater than 1.5 mol% and less than or equal to 3 mol%, or any and all subranges formed by any of these endpoints; and b* can be greater than or equal to 0 and less than or equal to 25, greater than or equal to 0 and less than or equal to 15, greater than or equal to 0 and less than or equal to 10, greater than or equal to 2.5 and less than or equal to 25, greater than or equal to 2.5 and less than or equal to 15, greater than or equal to 2.5 and less than or equal to 10, greater than or equal to 5 and less than or equal to 25, greater than or equal to 5 and less than or equal to 15, or even greater than or equal to 5 and less than or equal to 10, or any and all subranges formed by any of these endpoints.
[0136] In an embodiment, the glass composition and the resulting colored glass article may include greater than or equal to 60 mol % and less than or equal to 70 mol % SiO 2 ; greater than or equal to 11 mol% and less than or equal to 17 mol% Al 2 O 3 ; greater than or equal to 2 mol% and less than or equal to 8 mol% B 2 O 3 ; greater than or equal to 9 mol% and less than or equal to 14 mol% Li 2 O; greater than or equal to 2 mol% and less than or equal to 6 mol% of Na 2 O; 0.1 mol% or more and 0.5 mol% or less of K 2 O; and greater than or equal to 1×10 -6 mol% and less than or equal to 0.05 mol% Au. In these embodiments, R 2 O / Al 2 O 3 Greater than or equal to 0 mol% and less than or equal to 3 mol%, R 2 O is Li 2 O、Na 2 O and K 2 The sum of O.
[0137] Different color coordinates within the color gamut can be achieved by varying the heat treatment cycle used to produce the resulting colored glass article. The heat treatment cycle is characterized by the temperature of the environment (i.e., the oven) and the duration of the cycle (i.e., the time the glass article is exposed to the heated environment). As used herein, the phrase "temperature of the heat treatment cycle" refers to the temperature of the environment (i.e., the oven). In an embodiment, a glass article formed from a glass composition described herein is heat treated in an isothermal oven to produce a resulting colored glass article.
[0138] In an embodiment, the temperature of the thermal treatment cycle is greater than or equal to 500°C, greater than or equal to 550°C, greater than or equal to 575°C, greater than or equal to 600°C, greater than or equal to 625°C, or even greater than or equal to 650°C. In an embodiment, the temperature of the thermal treatment cycle is less than or equal to 800°C, less than or equal to 775°C, less than or equal to 750°C, less than or equal to 725°C, or even less than or equal to 700°C. In an embodiment, the temperature of the thermal treatment cycle is greater than or equal to 500°C and less than or equal to 800°C, greater than or equal to 500°C and less than or equal to 775°C, greater than or equal to 500°C and less than or equal to 750°C, greater than or equal to 500°C and less than or equal to 725°C, greater than or equal to 550°C and less than or equal to 700°C, greater than or equal to 550°C and less than or equal to 800°C, greater than or equal to 550°C and less than or equal to 775°C, greater than or equal to 550°C and less than or equal to 750°C, 550°C and less than or equal to 725°C, 550°C and less than or equal to 700°C, 575°C and less than or equal to 800°C, 575°C and less than or equal to 775°C, 575°C and less than or equal to 750°C, 575°C and less than or equal to 725°C, 575°C and less than or equal to 700°C, 600°C and less than or equal to 800°C, 600°C and less than or equal to 775°C, 600°C and less than or equal to 750°C, 600°C and less than or equal to 725°C, 600°C and less than or equal to 700°C, 625°C and less than or equal to 800°C, 625°C and less than or equal to 775°C, 625°C and less than or equal to 750°C, 625°C and less than or equal to 725°C, greater than or equal to 625°C and less than or equal to 700°C, greater than or equal to 650°C and less than or equal to 800°C, greater than or equal to 650°C and less than or equal to 775°C, greater than or equal to 650°C and less than or equal to 750°C, greater than or equal to 650°C and less than or equal to 725°C, or even greater than or equal to 650°C and less than or equal to 700°C, or any and all sub-ranges formed by any of these endpoints.
[0139] In an embodiment, the duration of the heat treatment cycle is greater than or equal to 0.25 hours, greater than or equal to 0.5 hours, greater than or equal to 1 hour, or even greater than or equal to 2 hours. In an embodiment, the duration of the heat treatment cycle is less than or equal to 24 hours, less than or equal to 16 hours, less than or equal to 8 hours, or even less than or equal to 4 hours. In embodiments, the duration of the heat treatment cycle is greater than or equal to 0.25 hours and less than or equal to 24 hours, greater than or equal to 0.25 hours and less than or equal to 16 hours, greater than or equal to 0.25 hours and less than or equal to 8 hours, greater than or equal to 0.25 hours and less than or equal to 4 hours, greater than or equal to 0.5 hours and less than or equal to 24 hours, greater than or equal to 0.5 hours and less than or equal to 16 hours, greater than or equal to 0.5 hours and less than or equal to 8 hours, greater than or equal to 0.5 hours and less than or equal to 4 hours, greater than or equal to 1 hour and less than or equal to 24 hours, greater than or equal to 1 hour and less than or equal to 16 hours, greater than or equal to 1 hour and less than or equal to 8 hours, greater than or equal to 1 hour and less than or equal to 4 hours, greater than or equal to 2 hours and less than or equal to 24 hours, greater than or equal to 2 hours and less than or equal to 16 hours, greater than or equal to 2 hours and less than or equal to 8 hours, or even greater than or equal to 2 hours and less than or equal to 4 hours, or any and all subranges formed by any of these endpoints.
[0140] The tinted glass articles formed from the glass compositions described herein can be of any suitable thickness, which can vary depending on the specific application of the tinted glass article. In embodiments, the tinted glass article can have a thickness of greater than or equal to 250 μm and less than or equal to 6 mm, greater than or equal to 250 μm and less than or equal to 4 mm, greater than or equal to 250 μm and less than or equal to 2 mm, greater than or equal to 250 μm and less than or equal to 1 mm, greater than or equal to 250 μm and less than or equal to 750 μm, greater than or equal to 250 μm and less than or equal to 500 μm, greater than or equal to 500 μm and less than or equal to 6 mm, greater than or equal to 500 μm and less than or equal to 4 mm, greater than or equal to 500 μm and less than or equal to 2 mm, greater than or equal to 500 μm and less than or equal to 1 mm, greater than or equal to 50 ...750 μm, greater than or equal to 250 μm and less than or equal to 500 μm, greater than or equal to 500 μm and less than or equal to 6 mm, greater than or equal to 500 μm and less than or equal to 4 mm 0 μm and less than or equal to 750 μm, greater than or equal to 750 μm and less than or equal to 6 mm, greater than or equal to 750 μm and less than or equal to 4 mm, greater than or equal to 750 μm and less than or equal to 2 mm, greater than or equal to 750 μm and less than or equal to 1 mm, greater than or equal to 1 mm and less than or equal to 6 mm, greater than or equal to 1 mm and less than or equal to 4 mm, greater than or equal to 1 mm and less than or equal to 2 mm, greater than or equal to 2 mm and less than or equal to 6 mm, greater than or equal to 2 mm and less than or equal to 4 mm, or even greater than or equal to 4 mm and less than or equal to 6 mm, or any and all sub-ranges formed by any of these endpoints.
[0141] As discussed above, the tinted glass articles formed from the glass compositions described herein may have increased fracture toughness, making the tinted glass articles more resistant to damage. In an embodiment, the tinted glass articles have a K measured by the CNSB method prior to ion exchange. IC The fracture toughness can be greater than or equal to 0.7 MPa·m 1 / 2 In an embodiment, the tinted glass article has a K value as measured by the CNSB method prior to ion exchange. IC The fracture toughness can be greater than or equal to 0.7 MPa·m 1 / 2 , greater than or equal to 0.8MPa·m 1 / 2 , greater than or equal to 0.9MPa·m 1 / 2 , or even greater than or equal to 1.0 MPa·m 1 / 2 .
[0142] In embodiments, the glass compositions described herein are ion exchangeable to facilitate strengthening of colored glass articles made from the glass compositions. In a typical ion exchange process, smaller metal ions in the glass composition are replaced or "exchanged" with larger metal ions of the same valence in a layer near the outer surface of a colored glass article made from the glass composition. The replacement of smaller ions with larger ions creates compressive stresses in the layer of the colored glass article made from the glass composition. In embodiments, the metal ions are monovalent metal ions (e.g., Li + , Na + , K + The ion exchange is achieved by immersing a glass article made from the glass composition in a bath of a molten salt containing at least one larger metal ion, which will replace the smaller metal ions in the colored glass article. Alternatively, other monovalent ions such as Ag + , Tl + , Cu + The like can be used to replace monovalent ions. One or more ion exchange methods for strengthening a colored glass article made from a glass composition may include contacting the colored glass article with an ion exchange medium. In an embodiment, the ion exchange medium may be a molten salt bath. For example, the ion exchange process may include, but is not limited to, immersion in a single bath or multiple baths of the same or different compositions, with optional washing and / or annealing steps between immersions.
[0143] When exposed to the tinted glass article, according to embodiments, the ion exchange solution (e.g., KNO 3 and / or NaNO 3The temperature of the molten salt bath) can be greater than, or equal to, 350°C and less than, or equal to, 500°C, greater than, or equal to, 360°C and less than, or equal to, 450°C, greater than, or equal to, 370°C and less than, or equal to, 440°C, greater than, or equal to, 360°C and less than, or equal to, 420°C, greater than, or equal to, 370°C and less than, or equal to, 400°C, greater than, or equal to, 375°C and less than, or equal to, 475°C, greater than, or equal to, 400°C and less than, or equal to, 500°C, greater than, or equal to, 410°C and less than, or equal to, 490°C, greater than, or equal to, 420°C and less than, or equal to, 480°C, greater than, or equal to, 430°C and less than, or equal to, 470°C, or even greater than, or equal to, 440°C and less than, or equal to, 460°C, or any and all subranges between the foregoing values. In an embodiment, the tinted glass article may be exposed to the ion exchange solution for greater than, or equal to, 2 hours and less than, or equal to, 2 hours and less than, or equal to, 12 hours, greater than, or equal to, 2 hours and less than, or equal to, 6 hours, greater than, or equal to, 8 hours and less than, or equal to, 24 hours, greater than, or equal to, 6 hours and less than, or equal to, 12 hours, greater than, or equal to, 8 hours and less than, or equal to, 24 hours, or even greater than, or equal to, 8 hours and less than, or equal to, 12 hours, or any and all subranges formed by any of these endpoints.
[0144] In an embodiment, a tinted glass article made from the glass composition may be ion exchanged to achieve a compression depth of 10 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, 90 μm or more, or 100 μm or more. In an embodiment, a tinted glass article made from the glass composition may have a thickness "t" and may be ion exchanged to achieve a compression depth greater than or equal to 0.15t, greater than or equal to 0.17t, or even greater than or equal to 0.2t. In an embodiment, a tinted glass article made from the glass composition may have a thickness "t" and may be ion exchanged to achieve a compression depth less than or equal to 0.3t, less than or equal to 0.27t, or even less than or equal to 0.25t. In an embodiment, a tinted glass article made from a glass composition described herein may have a thickness "t", and may be ion exchanged to achieve a compression depth greater than, or equal to, 0.15t and less than, or equal to, 0.3t, greater than, or equal to, 0.15t and less than, or equal to, 0.27t, greater than, or equal to, 0.15t and less than, or equal to, 0.25t, greater than, or equal to, 0.17t and less than, or equal to, 0.3t, greater than, or equal to, 0.17t and less than, or equal to, 0.27t, greater than, or equal to, 0.17t and less than, or equal to, 0.25t, greater than, or equal to, 0.2t and less than, or equal to, 0.3t, greater than, or equal to, 0.2t and less than, or equal to, 0.27t, or even greater than, or equal to, 0.2t and less than, or equal to, 0.25t, or any and all subranges formed by any of these endpoints.
[0145] The development of the surface compression layer is beneficial for obtaining better crack resistance and higher flexural strength compared to non-ion exchange materials. The surface compression layer has a higher concentration of ions exchanged into the tinted glass article than the concentration of ions exchanged into the tinted glass article of the main body of the tinted glass article (i.e., the area excluding the surface compression). In an embodiment, the surface compressive stress of the tinted glass article made from the glass composition after ion exchange strengthening may be greater than or equal to 300 MPa, greater than or equal to 400 MPa, greater than or equal to 500 MPa, or even greater than or equal to 600 MPa. In an embodiment, the surface compressive stress of the tinted glass article made from the glass composition after ion exchange strengthening may be less than or equal to 1 GPa, less than or equal to 900 MPa, or even less than or equal to 800 MPa. In an embodiment, a colored glass article made from the glass composition may have a surface compressive stress of greater than or equal to 300 MPa and less than or equal to 1 GPa, greater than or equal to 300 MPa and less than or equal to 900 MPa, greater than or equal to 300 MPa and less than or equal to 800 MPa, greater than or equal to 400 MPa and less than or equal to 1 GPa, greater than or equal to 400 MPa and less than or equal to 900 MPa, greater than or equal to 400 MPa and less than or equal to 800 MPa, greater than or equal to 500 MPa and less than or equal to 1 GPa, greater than or equal to 500 MPa and less than or equal to 900 MPa, greater than or equal to 500 MPa and less than or equal to 800 MPa, greater than or equal to 600 MPa and less than or equal to 1 GPa, greater than or equal to 600 MPa and less than or equal to 900 MPa, greater than or equal to 600 MPa and less than or equal to 800 MPa.
[0146] In an embodiment, the maximum central tension of the tinted glass article made from the glass composition after ion exchange strengthening may be greater than or equal to 40 MPa, greater than or equal to 60 MPa, greater than or equal to 80 MPa, or even greater than or equal to 100 MPa. In an embodiment, the maximum central tension of the tinted glass article made from the glass composition after ion exchange strengthening may be less than or equal to 250 MPa, less than or equal to 200 MPa, or even less than or equal to 150 MPa. In an embodiment, a tinted glass article made from the glass composition may have a maximum central tension greater than, or equal to, 40 MPa and less than, or equal to, 250 MPa, greater than, or equal to, 40 MPa and less than, or equal to, 200 MPa, greater than, or equal to, 40 MPa and less than, or equal to, 150 MPa, greater than, or equal to, 60 MPa and less than, or equal to, 250 MPa, greater than, or equal to, 60 MPa and less than, or equal to, 200 MPa, greater than, or equal to, 60 MPa and less than, or equal to, 150 MPa, greater than, or equal to, 80 MPa and less than, or equal to, 250 MPa, greater than, or equal to, 80 MPa and less than, or equal to, 200 MPa, greater than, or equal to, 80 MPa and less than, or equal to, 150 MPa, greater than, or equal to, 100 MPa and less than, or equal to, 250 MPa, greater than, or equal to, 100 MPa and less than, or equal to, 200 MPa, or even greater than, or equal to, 100 MPa and less than, or equal to, 150 MPa, or any and all subranges formed by any of these endpoints. As used herein, unless otherwise indicated, center tension refers to the maximum center tension value.
[0147] The tinted glass articles described herein can be used in a variety of applications, including, for example, back cover applications in consumer or commercial electronic devices such as smartphones, tablets, personal computers, ultrabooks, televisions, and cameras. Figure 1 and 2 An exemplary article comprising any of the tinted glass articles disclosed herein is shown in FIG. Figure 1 and Figure 2 A consumer electronic device 100 is shown, comprising a housing 102 having a front surface 104, a rear surface 106, and side surfaces 108; electronic components (not shown) at least partially within the housing or completely within the housing, and the electronic components include at least a controller, a memory, and a display 110, the display 110 being located at or adjacent to the front surface of the housing; and a cover substrate 112 at or on the front surface of the housing such that it is on the display. In an embodiment, at least a portion of the housing 102, such as the rear surface 106, may include any of the tinted glass articles disclosed herein.
[0148] Example
[0149] In order to more readily understand the various embodiments, reference is made to the following examples, which illustrate various embodiments of the tinted glass articles described herein.
[0150] Table 1 shows example compositions C1-C26, where the concentrations (in mol %) of the resulting colored glass articles were analyzed.
[0151] Table 1
[0152]
[0153] Table 1 continued
[0154]
[0155] Table 1 continued
[0156]
[0157] Table 1 continued
[0158]
[0159] Table 1 continued
[0160]
[0161] Referring now to Table 2, Example glass articles A1-A52 were formed from Example compositions C2-C9 and C15-C23 shown in Table 1 and subjected to heat treatment at the temperature and time period shown in Table 2. The transmittance color coordinates in the CIELAB color space measured under F2 illumination at an article thickness of 1.33 mm and a standard observer angle of 10°, and the observable color of the resulting colored glass articles are shown in Table 2.
[0162] Table 2
[0163]
[0164] Table 2 continued
[0165]
[0166] Table 2 continued
[0167]
[0168] Table 2 continued
[0169]
[0170] Table 2 continued
[0171]
[0172] Table 2 continued
[0173]
[0174] Table 2 continued
[0175]
[0176] Table 2 continued
[0177]
[0178] Table 2 continued
[0179]
[0180] Referring now to Table 3, Example glass articles A53-A114 were formed from Example compositions C1-C14 and C24-C26 shown in Table 1 and subjected to heat treatment at the temperatures and time periods shown in Table 3. The observable colors of the resulting colored glass articles are shown in Table 3.
[0181] Table 3
[0182]
[0183] Table 3 continued
[0184]
[0185] Table 3 continued
[0186]
[0187] Table 3 continued
[0188]
[0189] Table 3 continued
[0190]
[0191] Table 3 continued
[0192]
[0193] Table 3 continued
[0194]
[0195] Table 3 continued
[0196]
[0197] Table 3 continued
[0198]
[0199] Table 3 continued
[0200]
[0201] Table 3 continued
[0202]
[0203] Reference now Figure 3 and 4 The curves show the R 2 O-Al 2 O 3 Relationship with a* and b*. Figure 3 As shown, regardless of R 2 O-Al 2 O 3 For any value of a*, a* is positive, resulting in colors observable on the red side of the CIELAB color space. Figure 4 As shown, with R 2 O-Al 2 O 3 As , b* increases, causing the observable color to change from blue to yellow. 2 O-Al 2 O 3 The b* of Example glass products A35 and A36 formed from Example compositions C8 and C9 at 0.07 mol% and 0.04 mol%, respectively, were -9.39 and -8.92, respectively, resulting in a distinct purple glass product. 2 O-Al 2 O 3 Example glass compositions C2 and C3 at 2.98 mol % and 2.02 mol %, respectively, formed Example glass articles A29 and A30 having b* of 9.97 and 10.51, respectively, resulting in an observably orange glass article and an observably red glass article.
[0204] In addition, the Fe 2 O 3 and ZrO 2 Example glass articles A33 and A34 formed from example glass compositions C6 and C7, respectively, have an observable red color.
[0205] As shown in Tables 2 and 3 and Figure 3 and 4 As shown, the analyzed R 2 O-Al 2 O 3, additional components may be added to the glass composition, and the glass article may be subjected to certain heat treatments to provide the desired colored glass article.
[0206] It is obvious to those skilled in the art that various modifications and changes may be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Therefore, this specification is intended to cover modifications and changes of the various embodiments described herein, as long as such modifications and changes fall within the scope of the appended claims and their equivalents.
[0207] This application also relates to the following items.
[0208] 1. A colored glass product comprising:
[0209] 50 mol% or more and 80 mol% or less of SiO 2 ;
[0210] 7 mol% or more and 25 mol% or less of Al 2 O 3 ;
[0211] 1 mol% or more and 15 mol% or less of B 2 O 3 ;
[0212] 7 mol% or more and 20 mol% or less of Li 2 O;
[0213] 0.5 mol% or more and 12 mol% or less of Na 2 O;
[0214] K greater than 0 mol% and less than or equal to 1 mol% 2 O; and
[0215] Greater than or equal to 1×10 -6 mol% and less than or equal to 1 mol% Au, where:
[0216] R 2 O-Al 2 O 3 Greater than or equal to -5 mol% and less than or equal to 5 mol%, R 2 O is Li 2 O、Na 2 O and K 2 The sum of O.
[0217] 2. The tinted glass article according to item 1, wherein the transmittance color coordinates of the tinted glass article in the CIELAB color space, measured under F2 illumination with an article thickness of 1.33 mm and a standard observation angle of 10°, are:
[0218] L* is greater than or equal to 50 and less than or equal to 100;
[0219] a* is greater than or equal to -15 and less than or equal to 25; and
[0220] b* is greater than or equal to -25 and less than or equal to 25.
[0221] 3. The colored glass product according to item 2, wherein R 2 O-Al 2 O 3 Greater than or equal to −5 mol % and less than or equal to 1.5 mol %; and wherein b* is greater than or equal to −25 and less than or equal to 10.
[0222] 4. The colored glass product according to item 3, wherein R 2 O-Al 2 O 3 Greater than or equal to -3 mol % and less than or equal to 1.5 mol %; and wherein b* is greater than or equal to -15 and less than or equal to 7.
[0223] 5. The colored glass product according to item 2, wherein R 2 O-Al 2 O 3 greater than 1.5 mol % and less than or equal to 5 mol %; and wherein b* is greater than or equal to 0 and less than or equal to 25.
[0224] 6. The colored glass product according to item 5, wherein R 2 O-Al 2 O 3 greater than 1.5 mol % and less than or equal to 5 mol %; and wherein b* is greater than or equal to 0 and less than or equal to 15.
[0225] 7. The colored glass article according to any one of items 1 to 6, wherein R 2 O-Al 2 O 3 Greater than or equal to -3 mol% and less than or equal to 5 mol%.
[0226] 8. The colored glass product according to item 7, wherein R 2 O-Al 2 O 3 Greater than or equal to -1 mol% and less than or equal to 3 mol%.
[0227] 9. The tinted glass article according to any one of items 1 to 8, wherein the tinted glass article comprises greater than or equal to 0.0001 mol % and less than or equal to 0.1 mol % Au.
[0228] 10. The tinted glass article according to any one of items 1 to 9, wherein R 2 O is greater than or equal to 6 mol % and less than or equal to 25 mol %.
[0229] 11. The colored glass product according to item 10, wherein R 2 O is greater than or equal to 8 mol % and less than or equal to 23 mol %.
[0230] 12. The tinted glass article according to any one of items 1 to 11, wherein the tinted glass article comprises greater than or equal to 0.01 mol % and less than or equal to 2 mol % of ZrO 2 .
[0231] 13. The colored glass article according to item 12, wherein the colored glass article comprises greater than or equal to 0.1 mol % and less than or equal to 1.5 mol % of ZrO 2 .
[0232] 14. The tinted glass article according to any one of items 1 to 13, wherein the tinted glass article comprises greater than or equal to 0.01 mol % and less than or equal to 1 mol % of Fe 2 O 3 .
[0233] 15. The colored glass article according to item 14, wherein the colored glass article comprises greater than or equal to 0.05 mol % and less than or equal to 0.5 mol % of Fe 2 O 3 .
[0234] 16. The colored glass article according to any one of items 1 to 15, wherein 5.72*Al 2 O 3 (mol%)-21.4*ZnO(mol%)-2.5*P 2 O 5 (mol%)-35*Li 2 O(mol%)-16.6*B 2 O 3 (mol%)-20.5*MgO (mol%)-23.3*Na 2 O(mol%)-27.9*SrO(mol%)-18.5*K 2O (mol%) -26.3*CaO (mol%) is greater than -609 mol%.
[0235] 17. The colored glass article according to any one of items 1 to 16, wherein the colored glass article comprises greater than or equal to 0.01 mol % and less than or equal to 1 mol % of SnO 2 .
[0236] 18. The colored glass article according to item 17, wherein the colored glass article comprises greater than or equal to 0.05 mol % and less than or equal to 0.75 mol % of SnO 2 .
[0237] 19. The tinted glass article according to any one of items 1 to 18, wherein the tinted glass article is substantially free of MgO, CaO, ZnO, Cl or a combination thereof.
[0238] 20. The tinted glass article according to any one of items 1 to 19, wherein the tinted glass article comprises greater than or equal to 7 mol % and less than or equal to 18 mol % of Li 2 O.
[0239] 21. The colored glass article according to item 20, wherein the colored glass article comprises greater than or equal to 9 mol % and less than or equal to 16 mol % of Li 2 O.
[0240] 22. The tinted glass article according to any one of items 1 to 21, wherein the tinted glass article comprises greater than or equal to 1 mol % and less than or equal to 12 mol % of Na 2 O.
[0241] 23. The colored glass article according to item 22, wherein the colored glass article comprises greater than or equal to 2 mol% and less than or equal to 10 mol% of Na 2 O.
[0242] 24. The tinted glass article according to any one of items 1 to 23, wherein the tinted glass article comprises greater than or equal to 0.1 mol % and less than or equal to 0.5 mol % of K 2 O.
[0243] 25. The tinted glass article according to any one of items 1 to 24, wherein the tinted glass article comprises greater than or equal to 9 mol % and less than or equal to 23 mol % of Al 2 O 3 .
[0244] 26. The tinted glass article according to item 25, wherein the tinted glass article comprises greater than or equal to 11 mol % and less than or equal to 20 mol % of Al 2 O 3 .
[0245] 27. The tinted glass article according to any one of items 1 to 26, wherein the tinted glass article comprises greater than or equal to 2 mol % and less than or equal to 12 mol % of B 2 O 3 .
[0246] 28. The tinted glass article according to item 27, wherein the tinted glass article comprises greater than or equal to 3 mol % and less than or equal to 10 mol % of B 2 O 3 .
[0247] 29. The tinted glass article according to any one of items 1 to 28, wherein the tinted glass article comprises greater than or equal to 52 mol % and less than or equal to 75 mol % SiO 2 .
[0248] 30. The tinted glass article according to any one of items 1 to 29, wherein the thickness of the tinted glass article is greater than or equal to 250 μm and less than or equal to 6 mm.
[0249] 31. The tinted glass article according to any one of items 1 to 30, wherein the tinted glass article is an ion-exchanged tinted glass article.
[0250] 32. The tinted glass article of item 31, wherein the ion-exchanged tinted glass article has a compression depth of 10 μm or greater.
[0251] 33. The tinted glass article of item 31 or item 32, wherein the ion-exchanged tinted glass article has a thickness "t" and a compression depth greater than or equal to 0.15 t.
[0252] 34. The tinted glass article according to any one of items 30 to 32, wherein the surface compressive stress of the ion-exchanged tinted glass article is greater than or equal to 300 MPa.
[0253] 35. The tinted glass article of any one of items 30 to 33, wherein the ion-exchanged tinted glass article has a maximum central tension greater than or equal to 40 MPa.
[0254] 36. A consumer electronic device comprising:
[0255] a housing having a front surface, a rear surface, and side surfaces; and
[0256] an electronic component disposed at least partially within the housing, the electronic component comprising at least a controller, a memory, and a display, the display being disposed at or adjacent to a front surface of the housing;
[0257] wherein the housing comprises the tinted glass article of any one of items 1 to 35.
[0258] 37. A glass composition comprising:
[0259] 50 mol% or more and 80 mol% or less of SiO 2 ;
[0260] 7 mol% or more and 25 mol% or less of Al 2 O 3 ;
[0261] 1 mol% or more and 15 mol% or less of B 2 O 3 ;
[0262] 7 mol% or more and 20 mol% or less of Li 2 O;
[0263] 0.5 mol% or more and 12 mol% or less of Na 2 O;
[0264] K greater than 0 mol% and less than or equal to 1 mol% 2 O; and
[0265] Greater than or equal to 1×10 -6 mol% and less than or equal to 1 mol% Au, where:
[0266] R 2 O-Al 2 O 3 Greater than or equal to -5 mol% and less than or equal to 5 mol%, R 2 O is Li 2 O、Na 2 O and K 2 The sum of O.
[0267] 38. The glass composition according to item 37, wherein R 2 O-Al 2 O 3 Greater than or equal to -3 mol% and less than or equal to 5 mol%.
[0268] 39. The glass composition according to item 38, wherein R 2 O-Al 2 O 3 Greater than or equal to -1 mol% and less than or equal to 3 mol%.
[0269] 40. The glass composition according to any one of items 37 to 39, wherein the glass composition comprises greater than or equal to 0.0001 mol % and less than or equal to 0.1 mol % Au.
[0270] 41. The glass composition according to any one of items 37 to 40, wherein R 2 O is greater than or equal to 6 mol % and less than or equal to 25 mol %.
[0271] 42. The glass composition according to item 41, wherein R 2 O is greater than or equal to 8 mol % and less than or equal to 23 mol %.
[0272] 43. The glass composition according to any one of items 37 to 42, wherein the glass composition comprises greater than or equal to 0.01 mol % and less than or equal to 2 mol % of ZrO 2 .
[0273] 44. The glass composition according to item 43, wherein the glass composition comprises greater than or equal to 0.1 mol % and less than or equal to 1.5 mol % of ZrO 2 .
[0274] 45. The glass composition according to any one of items 37 to 44, wherein the glass composition comprises greater than or equal to 0.01 mol % and less than or equal to 1 mol % of Fe 2 O 3 .
[0275] 46. The glass composition according to item 45, wherein the glass composition comprises greater than or equal to 0.05 mol % and less than or equal to 0.5 mol % of Fe 2 O 3 .
[0276] 47. The glass composition according to any one of items 37 to 46, wherein 5.72*Al 2 O 3 (mol%)-21.4*ZnO(mol%)-2.5*P 2 O 5 (mol%)-35*Li 2 O(mol%)-16.6*B 2 O 3(mol%)-20.5*MgO (mol%)-23.3*Na 2 O(mol%)-27.9*SrO(mol%)-18.5*K 2 O (mol%) -26.3*CaO (mol%) is greater than -609 mol%.
[0277] 48. The glass composition according to any one of items 37 to 47, wherein the glass composition comprises greater than or equal to 0.01 mol % and less than or equal to 1 mol % of SnO 2 .
[0278] 49. The glass composition according to item 48, wherein the glass composition comprises greater than or equal to 0.05 mol % and less than or equal to 0.75 mol % of SnO 2 .
[0279] 50. The glass composition of any one of items 37 to 49, wherein the glass composition is substantially free of MgO, CaO, ZnO, Cl or a combination thereof.
[0280] 51. The glass composition according to any one of items 37 to 50, wherein the glass composition comprises greater than or equal to 7 mol % and less than or equal to 18 mol % of Li 2 O.
[0281] 52. The glass composition according to item 51, wherein the glass composition comprises greater than or equal to 9 mol % and less than or equal to 16 mol % of Li 2 O.
[0282] 53. The glass composition according to any one of items 37 to 52, wherein the glass composition comprises greater than or equal to 1 mol % and less than or equal to 12 mol % of Na 2 O.
[0283] 54. The glass composition according to item 53, wherein the glass composition comprises greater than or equal to 2 mol % and less than or equal to 10 mol % of Na 2 O.
[0284] 55. The glass composition according to any one of items 37 to 54, wherein the glass composition comprises greater than or equal to 0.1 mol % and less than or equal to 0.5 mol % of K 2 O.
[0285] 56. The glass composition according to any one of items 37 to 55, wherein the glass composition comprises greater than or equal to 9 mol % and less than or equal to 23 mol % of Al 2O 3 .
[0286] 57. The glass composition according to item 56, wherein the glass composition comprises greater than or equal to 11 mol % and less than or equal to 20 mol % of Al 2 O 3 .
[0287] 58. The glass composition according to any one of items 37 to 57, wherein the glass composition comprises greater than or equal to 2 mol % and less than or equal to 12 mol % of B. 2 O 3 .
[0288] 59. The glass composition according to item 58, wherein the glass composition comprises greater than or equal to 3 mol % and less than or equal to 10 mol % of B. 2 O 3 .
[0289] 60. The glass composition according to any one of items 37 to 59, wherein the glass composition comprises greater than or equal to 52 mol % and less than or equal to 75 mol % of SiO 2 .
[0290] 61. A method of forming a tinted glass article, the method comprising:
[0291] A glass composition is thermally treated to form a glass article, the glass composition comprising:
[0292] 50 mol% or more and 80 mol% or less of SiO 2 ;
[0293] 7 mol% or more and 25 mol% or less of Al 2 O 3 ;
[0294] 1 mol% or more and 15 mol% or less of B 2 O 3 ;
[0295] 7 mol% or more and 20 mol% or less of Li 2 O;
[0296] 0.5 mol% or more and 12 mol% or less of Na 2 O;
[0297] K greater than 0 mol% and less than or equal to 1 mol% 2 O; and
[0298] Greater than or equal to 1×10 -6 mol% and less than or equal to 1 mol% Au, where:
[0299] R 2 O-Al 2 O 3 Greater than or equal to -5 mol% and less than or equal to 5 mol%, R 2 O is Li 2 O、Na 2 O and K 2 The sum of O; and
[0300] The glass article is subjected to a heat treatment cycle at a temperature greater than or equal to 500° C. and less than or equal to 800° C. and a duration greater than or equal to 0.25 hours and less than or equal to 24 hours to produce the tinted glass article.
[0301] 62. The method according to item 61, wherein the temperature of the heat treatment cycle is greater than or equal to 550°C and less than or equal to 775°C.
[0302] 63. A method according to item 61 or item 62, wherein the duration of the heat treatment cycle is greater than or equal to 0.5 hours and less than or equal to 16 hours.
[0303] 64. The method of any one of items 61 to 63, further comprising strengthening the tinted glass article in an ion exchange bath at a temperature of 350°C or greater to 500°C or less for a period of time of 2 hours or greater to 12 hours or less to form an ion-exchanged glass-ceramic article.
[0304] 65. The method according to item 64, wherein the ion exchange bath comprises KNO 3 .
[0305] 66. The method according to item 65, wherein the ion exchange bath comprises NaNO 3 .
Claims
1. A glass composition comprising: 50 mol % or more and 80 mol % or less of SiO2; 7 mol% or more and 25 mol% or less of Al2O3; 1 mol% or more and 15 mol% or less of B2O3; 9 mol % or more and 20 mol % or less of Li2O; 0.5 mol% or more and 12 mol% or less of Na2O; K2O greater than 0 mol% and less than or equal to 1 mol%; Greater than or equal to 1×10 -6 mol% and less than or equal to 0.0016mol% Au; Less than 0.1 mol% MoO3; as well as Less than 0.1 mol% WO3; in: R2O-Al2O3 is greater than or equal to -5 mol% and less than or equal to 5 mol%, and R2O is the sum of Li2O, Na2O and K2O.
2. The glass composition according to claim 1, wherein R2O-Al2O3 is greater than or equal to -3 mol% and less than or equal to 5 mol%. 3 . The glass composition according to claim 1 , wherein the glass composition comprises greater than or equal to 0.0001 mol % and less than or equal to 0.001 mol % of Au.
4. The glass composition according to claim 1, wherein R2O is greater than or equal to 6 mol% and less than or equal to 25 mol%. 5 . The glass composition according to claim 1 , wherein the glass composition comprises greater than or equal to 0.01 mol % and less than or equal to 2 mol % of ZrO 2 .
6. The glass composition according to claim 1, wherein 5.72*Al2O3 (mol%) -21.4*ZnO (mol%) -2.5*P2O5 (mol%) -35*Li2O (mol%) -16.6*B2O3 (mol%) -20.5*MgO (mol%) -23.3*Na2O (mol%) -27.9*SrO (mol%) -18.5*K2O (mol%) -26.3*CaO (mol%) is greater than -609mol%.
7. The glass composition according to claim 1, wherein the glass composition comprises greater than or equal to 0.01 mol% and less than or equal to 1 mol% of SnO2.
8. The glass composition according to claim 1, wherein the glass composition comprises greater than or equal to 1 mol% and less than or equal to 12 mol% of Na2O.
9. The glass composition according to claim 1, wherein the glass composition comprises greater than or equal to 0.1 mol% and less than or equal to 0.5 mol% of K2O.
10. The glass composition of claim 1, wherein the glass composition comprises greater than or equal to 2 mol% and less than or equal to 12 mol% B2O3.
11. A colored glass product comprising the glass composition according to claim 1.
12. The tinted glass article of claim 11, wherein the transmittance color coordinates of the tinted glass article in the CIELAB color space, as measured under F2 illumination with an article thickness of 1.33 mm and a standard observation angle of 10°, are: L* is greater than or equal to 50 and less than or equal to 100; a* is greater than or equal to -15 and less than or equal to 25; and b* is greater than or equal to -25 and less than or equal to 25. 13 . The tinted glass article according to claim 11 , wherein the tinted glass article has a thickness greater than or equal to 250 μm and less than or equal to 6 mm.
14. The tinted glass article of claim 11, wherein the tinted glass article is an ion-exchanged tinted glass article.
15. The tinted glass article of claim 14, wherein the ion-exchanged tinted glass article has a compression depth of 10 μm or greater.
16. The tinted glass article of claim 14, wherein the ion-exchanged tinted glass article has a surface compressive stress greater than or equal to 300 MPa.
17. The tinted glass article of claim 14, wherein the ion-exchanged tinted glass article has a maximum central tension greater than or equal to 40 MPa.
18. A consumer electronic device comprising: a housing having a front surface, a rear surface, and side surfaces; as well as an electronic component disposed at least partially within the housing, the electronic component comprising at least a controller, a memory, and a display, the display being disposed at or adjacent to a front surface of the housing; wherein the housing comprises the tinted glass article of claim 14.
19. A method for heat treating the glass composition of claim 1, the method comprising: The glass composition is heat treated to form a glass article, the glass article being subjected to a heat treatment cycle at a temperature greater than or equal to 500° C. and less than or equal to 800° C. and a duration greater than or equal to 0.25 hours and less than or equal to 24 hours to produce the tinted glass article.
Citation Information
Patent Citations
Polychromatic article and method of making same
CN111479787A
Glass-ceramics and glasses
CN111511696A